Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Enhancing transportation system resilience under earthquake-induced geohazards: a framework for cross-regional rescue - Damin Zhou; Li Peng; Rui Guo; Zhousong Jiang; Muzi Li (Transportation Research Part D: Transport and Environment, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Five undescribed compounds isolated from Gerbera delavayi with their anti-inflammatory activity - Li Jiang; Yang Wang; Zeng-Dan Ran; Ding-Yan Lu; Rui-Xi Li; Jia Sun; Yong Huang; Xue Ma; Yong-Jun Li (Phytochemistry, 2026)

Fabrication of food-derived bigels beads for the co-delivery of hydrophobic and hydrophilic bioactives: insights into environmental responsiveness and release mechanisms - Rongrong Zhang; Rui Fan; Kai Qi; Jinchi Jiang; Mingzhou Yu; Yiyang Yu; Wenge Yang; Wenhui Li; Yonghong Hu (Food Research International, 2026)

Continuous versus discontinuous biodegradable film mulching in maize: A five-year field study on soil carbon sequestration, productivity, and microplastic legacy - Kai Wang; Xiao Li; Shiyan Sun; Gary Y. Gan; Ying Zhao; Qiang Li; Jiangxin Gu; Rui Jiang (Field Crops Research, 2026)

Managing nitrate pollution in mixed land-use watersheds: source attribution and removal revealed by isotopes and 15N pairing - Jian Zhang; Hao Jiang; Yanping Li; Wenshi Zhang; Wenlu Lan; Junlin Shu; Xin Luo; Rui Zhang; Ke Pan (Ecological Engineering, 2026)

NIR-responsive mesoporous core-shell nanoplatform with oxygen self-supply and cascade targeting for reversing doxorubicin resistance via synergistic chemo-phototherapy - Yufeng Li; Yuping Jiang; Kexuan Wang; Xinyi Liu; Rui Yang; Lu Han; Tao He; Na Li; Da Huo (Chemical Engineering Journal, 2026)

Impact of complex mountainous terrain on the development of strong convective storms: A WRF simulation case study in Southeastern Yunnan Province, China - Cong Jiang; Wenjie Jin; Xin Yin; Chen Li; Rui Mao; Liyun Yin (Atmospheric Research, 2026)

Microplastics-induced effects on membrane fouling and effluent quality in MBRs for landfill leachate treatment under long-term operation - Shijie Bian; Jingwei Yan; Timing Jiang; Huying Li; Rui Cai; Wen Li; Jingjing Shi; Fan Yang; Sha Liang; Huabo Duan; Wenbo Yu; Shushan Yuan; et al. (Waste Management, 2026)

Utilization of spent biochar as a novel adsorbent and catalyst for the removal of ciprofloxacin from water: Insights into the performance and mechanisms - Xiaohong Hu; Tao Jiang; Bing Wang; Rui Li (Journal of Environmental Chemical Engineering, 2026)

Co-inoculation of lactic acid bacteria improves silage quality and mitigates antibiotic resistance gene transmission by restructuring the microbial community in hybrid Pennisetum silage - Duoting Wu; Wan Zhong; Zhisheng Wang; Xinyan Tao; Liyuan Shi; Peng Dai; Fali Wu; Yahui Jiang; Quanhui Peng; Jianxin Xiao; Yiping Tang; Huawei Zou; et al. (Journal of Environmental Chemical Engineering, 2026)

Effect of food components on arsenic metabolism by the gut microbiota using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME) - Yue Wu; Shimao Xiong; Xiyan Jiang; Peng Xiao; Fang Zhao; Rui Li; Syed Ali Hassan; Xiaolin Cai; Zhengyi Hu; Dennis Sandris Nielsen; Naiyi Yin; Yanshan Cui (Food Research International, 2026)

Multi-omics combined with simulated fermentation model for elucidation of variation patterns of lipids and volatiles and its mechanism during black tea fermentation - Linchi Niu; Yuning Feng; Shan Zhang; Zhizhen Fang; Rui Liang; Zhenxing Xu; Xujiang Shan; Qinghua Zhou; Haibo Yuan; Yongwen Jiang; Jia Li (Food Chemistry, 2026)

Machine learning models reveal the spatial distribution and key environmental drivers of Coilia nasus in East China Sea's coastal waters - Zeyu Xiao; Jiarong Shen; Haoran Wang; Rijin Jiang; Jianxiong Li; Rui Yin; Jiaying Zeng; Mingyuan Cui (Estuarine, Coastal and Shelf Science, 2026)

Flow velocity and turbulent kinetic energy effects on Crassostrea ariakensis larval settlement: Lab and CFD insights - Nan-nan Li; Rui-liang Fan; Long-ling Ouyang; Yuan-ge Chen; Jia-feng Fang; Wei Jiang; Nian Wei; Wei-min Quan (Estuarine, Coastal and Shelf Science, 2026)

Rapid inverse design of double-curved beams for multi-stable metamaterials based on prescribed deformation histories through artificial neural network - Chun-Zheng Zhao; Xin Wang; Rui Zhang; Yongfeng Jiang; Haibo Ji; Zhen Li; Bingyang Li; Pengfei Wang; Feng Jin; Tian Jian Lu (Engineering Structures, 2026)

Targeting the oxidation-inflammation-senescence axis in osteoarthritis with a single-atom iridium nanozyme - Yunsheng Jiang; Rui Li; Yun Ning; Zhiyu Chen; Tao Li; Cheng Chen (Chemical Engineering Journal, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

Enhanced degradation of sulfamethoxazole in dielectric barrier discharge plasma via Zn tetrahedral site doping-mediated d-band center engineering of CoFe2O4 - Xiaojing Wang; Rui Cao; Na Huang; Mengmeng Du; Mingyao Yuan; Jia Ma; Fan Zhang; Jiaqi Jiang; Zhenxing Zeng; Yanzong Zhang; Zhilin Li; Shihuai Deng (Chemical Engineering Journal, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Equivalent emissivity correction of the blackbody on-board MWRI-RM - Dong Ke-Song; Xing Rui-Xian; Bai Chuan; XU Jing; Meng Wan-Ting; He Jia-Kai; Jiang Li-Fei (International Journal of Remote Sensing, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Research on the intelligent obstacle avoidance and path optimization approaches for ship navigation in ice regions - Zhichen Liu; Sihui Wu; Mingyuan Jiang; Ying Li; Rui Gao; Jianan Luo (Ocean Engineering, 2026)

Divergent effects of biodegradable and conventional microplastics on denitrification in soils: Mechanisms governing N₂O emission and product stoichiometry - Hao Zhang; Xiao Li; Minhang Zhu; Rui Wang; Jinbo Zhang; Christoph Müller; Rui Jiang (Journal of Hazardous Materials, 2026)

Adaptive genetic trade-offs govern the enantioselective degradation and horizontal transfer of ibuprofen catabolic genes - Weihao Zhu; Mingli Jiang; Rui Fan; Kaihua Pan; Shenghao Wang; Lu Huang; Qiantong Ru; Yinhu Jiang; Qian Li; Qian Zhu; Mingliang Zhang; Zhijian Ke; et al. (Journal of Hazardous Materials, 2026)

Interfacial electron redistribution stabilizes Cu-centered redox cycling for efficient Fenton-like catalysis - Xiao-Ying Li; Ruo-Lan Xu; Ren Zhu; Ting-Yu Zhang; Wen-Rui Wang; Wu-Jun Liu; Hong Jiang (Journal of Cleaner Production, 2026)

How phosphorus enrichment regulates the microbial community resistance and multifunctions tolerance to drying–rewetting cycles in paddy fields: the critical role of stoichiometry - Jiaying Wang; Yi Xu; Tinghong Fu; Guoxiang You; Rui Wang; Tianyun Li; Zewei Jiang; Shihong Yang (Journal of Environmental Management, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Sex-specific associations between prenatal PM2.5 exposure and reproductive hormone levels in offspring aged 1–2 years: A prospective birth cohort study - Wenpu Shao; Shengli Jiang; Yudiyang Ma; Ning Chen; Zhiping Niu; Rui Tang; Meiqi Xing; Lei Zheng; Xinru Zhao; Bin Sun; Haibo Li; Ziyi Zhou; et al. (Environmental Research, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Environment-responsive multi-enzymed Cu/Cu2O@NC nanorhombic nanoplatform for infected wound antimicrobial treatment - Ji Cheng; Hao Zhang; Yueting Jiang; Zuojia guo; Rui Liu; Xiantao Lin; Hanjin Lu; Yunjun zhang; Wenxuan Fan; Ding Luo; Jinghua Li (Chemical Engineering Journal, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Folic acid alleviates heat stress-induced ovarian dysfunction in dairy cows via modulation of follicular fluid metabolism and ABC transporter activity - Yaochang Wei; Yifan Yang; Yifan Li; Zhuangsheng Wang; Tingting Deng; Xiaojiao Hu; Xuefeng Jiang; Rui Xiao; Yanfang Wu; Suzhu Qing; Yongsheng Wang (Animal Reproduction Science, 2026)

Correction to: Antibacterial activity and mechanism of rutin in UV-A light treatment against Escherichia coli O157:H7 - Jiahui Wang; Yuzhang Zhu; Tao Liu; Xiangyu Hong; Mi Liu; Rui Zhou; Xianke Li; Mingguo Jiang; Lifang Yang (Archives of Microbiology, 2026)

A topology-aware direction-adaptive multitask evolutionary algorithm - Yuxin Chen; Lizhong Yao; Rui Li; Pengjie Qin; Peng Jiang; Jun Yi (Swarm and Evolutionary Computation, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Numerical study of the flow field effect of turbulent reef units under different deployment configurations - Jiayi Wang; Rui Pan; Zhu Li; Xiaoran Liu; Qiwen Liang; Zhaoyang Jiang (Ocean Engineering, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

From acute defense to prolonged metabolic homeostasis: Insights into microalgae responses to PVC microplastic exposure - Jia Liang; Xiao Tan; Jiawei Li; J. Paul Chen; Yuanyuan Tang; Zhipeng Duan; Jiang Huang; Rui Zhu (Journal of Hazardous Materials, 2026)

Mitigating bioaerosol exposure risks in high-traffic clinics: Experimental and numerical optimization of air purifier interventions - Yongxin Wang; Zhijian Liu; Lei Jiang; Zirun Shi; Zijian Li; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Journal of Hazardous Materials, 2026)

Magnetite-phase steel slag-peroxymonosulfate promoted volatile fatty acids recovery from anaerobic fermentation of food waste: Substrates structure disruption and metabolic regulation - Xiupeng Jiang; Wei Wang; Youcai Zhao; Wenxiao Zhang; Xi Li; Rui Zhang; Xiaoya Li; Tao Zhou (Journal of Environmental Chemical Engineering, 2026)

Water and nutrient mechanism of bioretention systems under plant-filler synergy and seasonal dynamic regulation - Chunbo Jiang; Rui He; Jian Yuan; Hong Chen; Jiake Li (Journal of Environmental Chemical Engineering, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Defect-engineered Bi2O2S/Co3O4 heterostructure on sunflower pith for synergistic solar-driven interfacial evaporation and VOC degradation - Tingting Jiang; Siyu Huang; Zhuo Li; Rui Zhao; Haifeng Zhang (Chemical Engineering Journal, 2026)

Development of a triplex RT-qPCR assay for rapid and accurate detection of porcine rotavirus, porcine epidemic diarrhea virus, and porcine deltacoronavirus - Yuhan Yang; Xingyu Xiao; Meixuan Ren; Ningning Jiang; Xiaoxu Xie; Xue Zheng; Rui Yin; Shiyu Luan; Jingnan Wang; Peng Li (Veterinary Research Communications, 2026)

Microbial inoculation in green roofs: progress, challenges and ecological regulation strategies - Nan Yang; Hechen Li; Yihan Wang; Pingrui Jiang; Shaobo Gao; Hongyuan Li; Rui Hua; Xinjian Shi; Guang Hao (Urban Ecosystems, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

MECP2T203M mutation disrupts neurogenesis in human cerebral organoids by altering chromatin dynamics and transcriptional regulation - Zhihong Song; Qian Zhu; Rui Yang; Huihui Jiang; Ying Li; Liping Chen; Ting Wang; Yan Wu; Yan Liu; Haitao Wu (Science China Life Sciences, 2026)

Antibacterial activity and mechanism of rutin in UV‑A light treatment against Escherichia coli O157:H7 - Jiahui Wang; Yuzhang Zhu; Tao Liu; Xiangyu Hong; Mi Liu; Rui Zhou; Xianke Li; Mingguo Jiang; Lifang Yang (Archives of Microbiology, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Cross-species comparative transcriptomic analysis of spermatozoa reveals species-specific regulatory networks linked to fertilization-associated genes in cattle, sheep and goats - Yue Zhao; Linfeng Bai; Qiqi Jiang; Hao Xiao; Fangyuan Liu; Bilige Wuyun; Rihan Wu; Chunxia Hao; Rui Ding; Peng Yuan; Lizhi Wang; Ying Lu; et al. (Science China Life Sciences, 2026)

Lithium Enhances Survival Bias Associated with the Lateral Habenula Suppression - Kunlin Liu; Rui Zhu; Haoyue Guo; Jinghuan Li; Qianfu Wang; Yi He; Chenggang Zhu; Zheng Ma; Xiaodan Jiang; Jack van Honk; Jin Bao (Neuroscience Bulletin, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Micro-nano biochar interfaces promote adsorption-reduction coupling to accelerate bioelectrodechlorination in groundwater - Zena Zhang; Miao Lv; Rui Wang; Bo Wang; Ruoyu Du; Yuxuan Lou; Chunlin Wang; Xiaodun Jiang; Hai Hou; Zhiling Li; Fan Chen (Journal of Hazardous Materials, 2026)

Study on the synergistic effect of coal-oil co-liquefaction and analysis of liquefied oil products - Jin Jiang; Guanghua Yang; Ting Liu; Xiaodong Zhou; Xiaohui Li; Rui Sheng; Lang Liu (Fuel, 2026)

CO2-temperature-water nexus reshaping cherry tomato flavor: Multimodal sensing with E-nose and GC-IMS - Rui Li; Xinru Ren; Yilin Wang; Mengyan Jiang; Rongqun Wang; Zhi Zhang (Food Chemistry, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Evaluation of the aerosol transmission patterns and the airflow organization effectiveness in the respiratory outpatient clinic - Yongxin Wang; Lei Jiang; Zhijian Liu; Duo Cai; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Building and Environment, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Short-term organic fertilizer substitution: effects on crop yield and soil phosphorus dynamics in a rice-rapeseed rotation system - Hui Wang; Wenlong Cheng; Shang Han; Shan Tang; Fahui Jiang; Rongyan Bu; Min Li; Rui Zhu; Mengmeng Tang; Zhenghua Xu; Ji Wu (Journal of Soils and Sediments, 2026)

Vitamin C mitigates early auditory cortical hyperexcitability and antioxidant imbalance induced by acute intermittent hypoxia - Yue Wu; Tao Li; Wanxin Cao; Rui Fan; Hailing Jiang; Jiachen Han; Furong Ma; Yan Yan (Experimental Brain Research, 2026)

Dihydromyricetin attenuates LPS-induced liver injury in chicks through the JNK signaling pathway - Lina Jia; Jiarui Liu; Zhenghua Ji; Liang Yuan; Yingchao Gong; Xinru Jiang; Xianan Fan; Changwen Li; Rui Li; Haoran Wang; Fangping Liu (Research in Veterinary Science, 2026)

Report on the complete mitochondrial genome of the critically endangered and endemic Lauraceae plant Syndiclis anlungensis in China - Lang Huang; Dongzhen Jiang; Yanbing Yang; Rui Chen; Zhi Li; Lei Zhou; Xu Xiao (Plant Gene, 2026)

An adaptive spatiotemporal coupling approach for dynamic collision risk perception and quantification in intelligent vessels - Zhichen Liu; Mingyuan Jiang; Ying Li; Rui Gao; Yu Du; Jianan Luo (Ocean Engineering, 2026)

Centralized mechanical e-waste dismantling is associated with lower farmland soil heavy metal pollution and carbon emission intensity - Yu Zhang; Ming-jiang He; Wei-jun Fu; Jie Wang; Ke-li Zhao; Xiang-rui Xu; Ji-zi Wu (Journal of Environmental Chemical Engineering, 2026)

Genome-wide association study of wheat (Triticum aestivum L.) starch pasting properties - Jiahui Jiang; Hao Chang; Yongji Ma; Rui Jin; Rui Yu; Zhenhua Lu; Tianqi Bai; Yufeng Xu; Ruili Gou; Chengyu Lian; Wenting Zhang; Yingang Hu; et al. (Journal of Cereal Science, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Relationship of catalytic performance and catalyst structure evolution based on pressurized CH4-CO2 reforming reaction over carbon-supported Co-Ir alloy catalysts - Wen Tang; Jing-Pei Cao; Xiao-Yan Zhao; Dan Xie; Kai-Rui Luan; Chang-Jiang Li; Qi-Ming She; Tungalagtamir Bold (Fuel, 2026)

Linking environmental concentrations to cytotoxic mechanisms in second-hand vapor exposure of electronic cigarette via an integrated approach for in vitro toxicity assessment - Tong Cui; Yanpeng Li; Rui Lu; Zhenyu Niu; Xingtao Jiang (Environmental Pollution, 2026)

Mimicking leaves hierarchical differential pore architecture integrated with electric/magnetic inverse gradient structure for green EMI shielding and thermal infrared stealth - Dingwen Yin; Jinbao Li; Rui Cheng; Huijuan Xiu; Gengmei Liu; Feiguo Hua; Xuanchen Jiang; Yuxin Qin; Xia Wang (Chemical Engineering Journal, 2026)

Coordinatively robust and toughen plant protein adhesives via the synergy of oligomer domain cross-linking and hierarchical dissipation architecture - Wujie Huang; Zhenghui Lei; Ao zhang; Rui Xu; Jiawei Shao; Xianwei Wang; Shuaicheng Jiang; Jianzhang Li; Xiaona Li (Chemical Engineering Journal, 2026)

Interface-engineered MXene/OCNT fibers for high-performance wearable supercapacitors - Rui Wang; Xupu Jiang; Ting Ding; Wujun Ma; Chuntao Lan; Min Li (Chemical Engineering Journal, 2026)

Multi-scale evaluation of ERA5-land downward shortwave radiation and its implications for building energy simulation over China - Song Jiang; Jingfu Cao; Mingcai Li; Rui Miao; Minjie Yu (Theoretical and Applied Climatology, 2026)

Diffusion Model-Based Multi-Channel EEG Representation and Forecasting for Early Epileptic Seizure Warning - Zekun Jiang; Wei Dai; Qu Wei; Ziyuan Qin; Rui Wei; Mianyang Li; Xiaolong Chen; Ying Huo; Jingyun Liu; Kang Li; Le Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Global evaluation of the IRI-2020 ionospheric model using multi-source observations in 2022 - Chunhua Jiang; Rui Gao; Liang Chen; Huizhong Zhu; Min Li; Xiang Gao (Advances in Space Research, 2026)

Metabolic inflexibility across heart failure phenotypes: mechanisms and type-specific therapeutic implications - Li Chen; Xin-Rui Yang; Yan Jiang; Shi-Qi Cheng; Zhen-Xun Wan; Jin-Wen Wu; Ming-Tai Chen; Yuan-Yuan Li; Gang Luo; Meng-Nan Liu (Apoptosis, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

New 14,15-dinor- neo -clerodane and neo -clerodane diterpenoids from Ajuga macrosperma Wall. ex benth - Yi-huan Li; Yi-hang Ba; Jian-fen Xiao; Shuai Chen; Tian-qing Zhu; Kai-xiang Liu; Hong-ping He; Hua-yi Jiang; Rui Yang (Natural Product Research, 2026)

Hormonally and chemically induced male-to-female sex reversal is independent of Y-chromosome number in common carp - Kuangxin Chen; Yuanqi Guo; Yi Rong; Zhaoxian Li; Mouyan Jiang; Rui Li; Xiya Zhang; Yongming Li; Yulai Wei; Yanlong Song; Ji Chen; Binbin Tao; et al. (Aquaculture, 2026)

An automated vertebral heart scale measurement tool based on deep learning: Facilitating screening for prevention of canine cardiomegaly - Jing Chang; Rui Qin; Huijie Jiang; Jinfan Wei; Haotian Gong; Shijun Li; He Gong; Shuang Zhang (Preventive Veterinary Medicine, 2026)

A preliminary assessment of ocean wave parameter retrieval and wave energy estimation using spaceborne BDS-R data - Jinwei Bu; Shuhui Liu; Shunshuang Xu; Hui Yang; Tongsu Xiang; Xin He; Yuhang Jiang; Rui Li (Ocean Engineering, 2026)

Shift in orbital-scale climate response under the coupling of ice sheet and monsoon during the Late Oligocene: Sedimentary records from the East China Sea Shelf Basin - Yingkun Cui; Fujie Jiang; Xianke He; Yichen Liu; Wenji Wang; Rui Zhang; Yinghui Liu; Zhuo Li; Zhenguo Qi; Bo Xu; Hang lv; Jiming Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Extreme rainfall intensifies nitrogen responses through baseflow in arid and semi-arid river basins - Jinghui Dou; Rui Xia; Zixuan Tang; Zhen Huang; Xiaohui Jiang; Kai Zhang; Lina Li; Chao Yan (Journal of Hydrology, 2026)

A machine learning approach coupling immediate and lagged drivers to predict sand and dust storms in Northern China - Mile Wang; Kunxia Yu; Peng Li; Zhanbin Li; Rui Yan; Zixia Jiang; Xue Li; Lu Jia (Journal of Environmental Management, 2026)

Ultra-low temperature adsorption of propane to achieve layered Ni3V2O8/NiO synergistic catalysed oxidative dehydrogenation of propane to propylene - Rui Liao; Yun Yang; Peiting Jiang; Fengyu Ji; Yuhang Qian; Lulu Li; Xuyu Wang; Xinwei Zhou; Hongbing Ji (Fuel, 2026)

Superabsorbent and antimicrobial cryogel pads based on gelatin, sodium alginate and zinc oxide nanoparticles: Preparation, characterization and enhanced preservation of aquatic products - Jiaxuan Fang; Siyu Wu; Xiali Zeng; Rui Li; Zhenting Huo; Zhongjie Yu; Qingbao Ma; Di Sun; Yu Liu; Wei Jiang (Food Research International, 2026)

Co-fermentation with autochthonous Levilactobacillus brevis and Lactiplantibacillus plantarum modulates metabolome and volatile profiles to improve the quality and safety of fermented chopped chili - Wenkai Jiang; Qian Yang; Luyao Xiao; Xia Fan; Menghan Zhong; Mahsa Ghahvechi Chaeipeima; Kai Ma; Changliang Zhang; Xin Rui; Wei Li (Food Research International, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Strain-specific effects of infant-derived Bifidobacterium on gut microbiota modulation and mucus barrier responses in Salmonella infection - Xiaogan Zhao; Mahsa Ghahvechi Chaeipeima; Luyao Xiao; Xia Fan; Wenkai Jiang; Xiran Jia; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Bioscience, 2026)

Biotransport and biotransformation of arsenic in earthworm tissues: Advancing vermiremediation strategies of soil contamination - Yunxiang Xu; Muyuan Wang; Yizhao Wu; Yifan Zhang; Rui Jiang; Qi Zhao; Jibao Jiang; Hao Qiu; Yinsheng Li (Chemical Engineering Journal, 2026)

A Novel Elastoplastic Dynamic Damage Constitutive Model and Numerical Implementation of Rock Under True Triaxial Multistage Disturbance - Zhi Zheng; Yihuai Zhang; Guoxiong Mei; Haibo Jiang; Wei Wang; Rui Pan; Shaojun Li (Rock Mechanics and Rock Engineering, 2026)

Identification, expression, and insecticidal activity analysis of a novel cry toxin gene from Bacillus thuringiensis Gxun777-1 - Qi Gao; Tianbao Yang; Xixi Li; Rui Chen; Mingguo Jiang; Yan Zhou (World Journal of Microbiology and Biotechnology, 2026)

Evaluation and characterization of aphid (Aphis craccivora) resistance in selected alfalfa genotypes - Xin Jiang; Jing Tian; Gang Li; Guy Smagghe; Zhong-Yi Li; Dao-Chao Jin; Zhou Li; Rui Dong; Xin-Yao Gu (Crop Protection, 2026)

Effects of bacteria-microalgae immobilization on physiology, immunity, microbial composition, and vibriosis resistance of sea cucumber (Apostichopus japonicus) - Xuda Wang; Zunchun Zhou; Ying Dong; Rui Mi; Jingwei Jiang; Danni Liu; Bo Ye; Xiaoyue Wang; Zhenjun Zhao; Boxue Yang; Shilei Li (Aquaculture, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Erlvejunzuo, a gallic acid-derived thiadiazole, inhibits glucose biosynthesis and confers broad-spectrum antifungal activity - Manman Zhang; Chengke Zhang; Yihan Jiang; Li Wu; Rui Zhang; Fengquan Liu; Cheng Li (Pesticide Biochemistry and Physiology, 2026)

Effect of densification on dimensional stability and water absorption behavior of pine - Ning Jiang; Xintao Zhao; Qingchuan Lu; Emily Treacher; Alberto Leonardi; Xuejiao Li; Rui Li; Zhongsen Zhang; Thomas James Marrow (Journal of Cleaner Production, 2026)

Secondary salinization in facility agricultural soils detrimentally affects the spatial distribution of earthworm communities: dominant drivers and ecological risks - Yifan Zhang; Yizhao Wu; Muyuan Wang; Rui Jiang; Yunxiang Xu; Qi Zhao; Jibao Jiang; Ke Song; Weiguang Lv; Yinsheng Li (Journal of Environmental Management, 2026)

Immobilization of arsenic and antimony in contaminated soil by nano silica–biogenic Fe (Hydr)oxide composites: Soil properties and microbial community impacts - Rui Xu; Chenyang Yin; Qian Li; Guangfei Qu; Zhenguo Wu; Lang Liao; Zhe Yin; Yan Zhang; Yongbin Yang; Tao Jiang (Journal of Environmental Chemical Engineering, 2026)

Triple-synergistic nanotherapeutics for acute and chronic colitis management via programmable multidimensional modulation - Penghui Wang; Yue Zhao; Ning Tian; Xiangling Liu; Tenghui Tian; Difu Zhu; Fangbing Liu; Hengyan Liu; Ling Li; Zhiyu Ren; Deok Chun Yang; Lei Zhao; et al. (Chemical Engineering Journal, 2026)

Functionalizing 3D DNA crystals by replacing non-framework strands - Xinyu Feng; Li Xu; Yunhan Zhang; Shuheng Wei; Dongbao Yao; Huichao Chen; Yueye Wang; Yujing Wu; Hui Hou; Xiao Cui; Qian Meng; Yue Gu; et al. (Chemical Engineering Journal, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Trpa1 activation suppresses luteinizing hormone via Activin/Follistatin Axis under cold stress in Nile Tilapia - Jing Li; Haomiao Dong; Zhikai Cao; Rui Dong; Quan Jiang (Aquaculture, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Alpaca nanobody-based sandwich ELISA for specific detection of Salmonella enteritidis in chicken - Liang Yuan; Shibo Wang; Yani Ren; Zhenghua Ji; Xinru Jiang; Beili Hao; Shuangshuang Hao; Xiaoxi Han; Changwen Li; Yicong Chang; Rui Li; Fangping Liu (Food Control, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Bioengineered functional scaffolds co-loaded with osteonectin and HA-internalizing osteoblasts for boosting bone regeneration - Wei Yang; Qin Zou; Chenxin Wang; Yuankun Ren; Rui Zhang; Mingyue Lin; Xueqi Zhang; Yu Liu; Boyang Wang; Wei Li; Li Jiang; Xiyu Li (Chemical Engineering Journal, 2026)

How biodegradable mulching alters soil nitrogen transformations to enhance soil nitrogen supply and influence gas emissions in a maize cropping system - Hao Zhang; Kai Wang; Jinbo Zhang; Christoph Müller; Dianyuan Ding; Qiang Li; Hengliang Tang; Rui Jiang (Plant and Soil, 2026)

Glaucine suppresses IL-16/CD4 to alleviate neuropathic pain via spinal p56lck-NMDA receptor signaling - Xue Li; Rui Wang; Xiaonan Ma; Jin Yang; Shen Zhang; Zimeng Zhang; Han Jiang; Jihua Liu; Boyang Yu; Wenling Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Anthropogenic heat amplification in industrial zones: Unraveling heat stress risk heterogeneity in river-sea dual-core cities - Yujie Li; Jingfu Cao; Mingcai Li; Song Jiang; Jie Yang; Rui Xin; Ping Qu; Jing Chen; Jing Wang (Sustainable Cities and Society, 2026)

The impact of precipitation and exposed rocks on the soil and water leakage processes in the karst depressions-sinkhole system: Insights from a laboratory simulation experiment - Feiyang Cai; Rui Li; Jiang Yuan; Benjin Yu (Soil and Tillage Research, 2026)

A bHLH transcription factor negatively regulates effective panicle number and grain yield by modulating auxin transport and distribution in rice - Tao Yang; Rui Zhu; Jinlong Li; Yulong Wang; Lei Zhou; Qiaoqiao Zhao; Ningjia Jiang; An Zeng; Yanli Qin; Haixia Liu; Chenyu Xia; Shichen Han; et al. (Molecular Plant, 2026)

Determining the source contributions of dissolved organophosphorus compounds in lake water utilizing FT-ICR-MS and PCA-APCS-MLR receptor models - Xinrui Jiang; Yao Du; Mengze Li; Rui Xu; Tianming Wu; Baisong Deng; Dandan Si; Wen Zhang; Jingwen Yu; Yanxin Wang (Journal of Hydrology, 2026)

Associations of prenatal exposure to organophosphate, pyrethroid, and neonicotinoid insecticides with maternal and infant urinary reproductive hormones - Ying Li; Ying Jiang; Ruizhen Li; Sha Huang; Ruijia Li; Qing Guo; Pei Leng; Rui Ma; Dingye Zheng; Yuanyuan Li; Shunqing Xu; Wei Xia (Journal of Hazardous Materials, 2026)

Performance analysis of an ammonia-kerosene dual-fuel novel SOFC-turboprop engine aviation hybrid system with chemical heat recovery - Xinyan Xiu; Rui Wang; Cong Wang; Jiwei Fang; Meng Zhao; Chenghao Li; Sibo Wang; Jiang Qin; Hongyan Huang (Fuel, 2026)

Machine learning-enhanced colorimetric and surface-enhanced Raman scattering-based bimodal lateral flow immunoassay for sensitive and simultaneous detection of the residues of lomefloxacin, ofloxacin, and pefloxacin - Minghui Li; Daqi Chen; Yuhuai Guo; Tianxu Li; Wenjie Guo; Rui Feng; Dien Shao; Ziqi Jiang; Ye Li; Jie Zan (Food Chemistry, 2026)

Efficient elimination of highly lethal Vibrio parahaemolyticus in shrimp aquaculture by a vibriophage - Mingrui Li; Huaijin Jiang; Keming Shi; Haoyu Huang; Xiaojun Wang; Fang Li; Ke Pan; Yunlan Yang; Rui Zhang (Fish & Shellfish Immunology, 2026)

Self-adaption ultra-small coordination polymer-incorporated nanofibers for multipronged management of diabetic wounds - Peirong Zhou; Min Jiang; Silei Li; Xuemin Ma; Yajuan Hu; Junliang Chen; Yun He; Gang Tao; Rui Cai (Chemical Engineering Journal, 2026)

Molecular dipole engineering enabled TiO2 electron transport layers for stable quantum-dot light-emitting diodes - Hang Liu; Pei-Li Gao; Bo Li; Hui Bao; Yin-Man Song; Meng-Wei Wang; Ting Ding; Jing Jiang; Rui-Feng Zheng; Feng-Jia Fan; Hai-Zheng Zhong; Kar-Wei Ng; et al. (Chemical Engineering Journal, 2026)

A new isoflavone from processed root barks of Paeonia suffruticosa and their procoagulant activity - Shuo-Guo Li; Rui Yang; Mi-Mi Lu; Shu-Mei Wang; Jiang Meng (Natural Product Research, 2026)

Enhancing geohazard susceptibility mapping with a sample reliability algorithm: a case study in Guangzhou, China - Yuchao Jiang; Yan Gao; Wenlong Li; Rui Chen; Zhiliang Zhang; Quan Yuan; Daixun He (Bulletin of Engineering Geology and the Environment, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Performance evaluation of an enhanced air-lift internal circulation anaerobic–aerobic integrated reactor for treating real domestic wastewater - Yi Jiang; Muhammad Younas; Rui Zhang; Yizhi Zhang; Siyi Bian; Mingjie Hu; Die Liang; Linshan Yang; Pan Li; Suhui Xia; Wenyang Tao; Yuji Ma; et al. (Journal of Water Process Engineering, 2026)

Migration and transformation mechanism and ecotoxicity of heavy metals in shale gas exploitation: Research progress and challenges - Hualin Zhang; Xiaoliang Jiang; Rui Wang; Tinggang Li (Journal of Hazardous Materials, 2026)

Developing a radio frequency disinfestation technology for red jujubes with BaTiO3 as a filling material: Pest mortality, energy efficiency, and product quality - Xin Ye; Junjie Zheng; Jinsong Zhang; Longlong Jiang; Rui Li; Shaojin Wang (Journal of Food Engineering, 2026)

Photocatalytic carbon dots for food-borne hazards: Antimicrobial and degradation mechanisms and applications in the food industry - Dangfeng Wang; Wangqing Jiang; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Hongyan Guo; Fangchao Cui; Xuepeng Li; Tingting Li; Jianrong Li (Food Research International, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Integrated Aerobic Exercise and Multisensory Environment Training for Age-related Cognitive Decline via Hippocampal-prefrontal Neural Circuit Modulation - Huawei Lin; Yuxi Qiu; Zhongyi Hu; Liming Chen; Yaling Dai; Tao Jiang; Rui Li; Sinuo Wang; Yajun Cao; Jianhong Li; Huanhuan Liu; Yuwei Ye; et al. (Molecular Neurobiology, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Spatial aggregation trends of cultivated land quality and landscape patterns: A remote sensing analysis - Mengmeng Tang; Wenlong Cheng; Zhengbao Gao; Fahui Jiang; Shang Han; Danyang Xu; Rongyan Bu; Shan Tang; Rui Zhu; Min Li; Hui Wang; Changai Lu; et al. (Applied Soil Ecology, 2026)

Dielectric heating technology assisted for multi-objective processing of agricultural products: research progress, challenges, and future perspectives - Mengge Li; Yingqi Tian; Gaoji Yang; Liumin Fan; Longlong Jiang; Rui Li; Shaojin Wang (Critical Reviews in Food Science and Nutrition, 2025)

Overexpression of the cold-repressed StWRKY70 enhances cold-induced sweetening resistance by coordinately attenuating starch-to-sugar conversion and increasing respiratory pathways - Rui Jiang; Chunyan Jiang; Xinyu Ni; Shuting Hu; Xiaoshuang Cui; Danting Li; Hui Sun; Tong Zhou; Jichun Wang; Dianqiu Lv; Xun Liu (Postharvest Biology and Technology, 2025)

Retention-driven water flow regulation: A network perspective - Xuan Jiang; Jinsong Zhao; Zhiwen Cai; Jiating Li; Jian Wang; Ling Wang; Xiao Li; Rui Hao; Shuxia Yu; Zhihua Shi (Journal of Environmental Management, 2025)

All-solid-waste-based non-sintered ceramsite prepared from coal fly ash and dechlorinated municipal solid waste incineration fly ash: performance and hydration mechanisms - Kai Xu; Xinyuan Zhan; Yan Wang; Jie Wang; Rui Deng; Rui Wang; Chen Li; Shui Jiang; Xiaomoli Li; Jingyu Li; Yuxi Zhang (Journal of Environmental Management, 2025)

PMTFIM: Integrating machine learning with nutrient balance theory to estimate multi-stage paddy fertilization information at field scale over large regions - Housheng Wang; Xiang Gao; Wei Jiang; Xuerong Lang; Xian Hu; Meihua Qiu; Qiankun Guo; Yonghong Liang; Xuelei Wang; Yue Mu; Rui Ren; Ganghua Li; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Hierarchical spatiotemporal delivery system reprograms osteoclast subtypes to promote angiogenesis and bone regeneration in steroid-induced osteonecrosis of the rat femoral head - Hongyu Quan; Taiyang Li; Chencan Ren; Yuwei He; Hongkun Xie; Zibo He; Rui Wang; Haibin Ding; Jinbao Li; Shiwu Dong; Hong Jiang (Chemical Engineering Journal, 2025)

Effect of turbulence induced shear on continuous synthesis of imidazolium ionic liquid 1-butyl-3-methylimidazolium bromide ([BMIM]Br) in a high shear rate Taylor-Couette flow reactor - Rui Jiang; Guang Li; Bin Li; Yanhong Guo; Xiaogang Yang (Chemical Engineering Journal, 2025)

Engineering V-based Prussian blue analogue cathodes toward ultrahigh capacity and rate capability in aqueous zinc-ion batteries - Yan Chen; Na Shen; Xinyu Guo; Chang Li; Chengcheng Zhu; Nan Jiang; Xi Liu; Wenjun Deng; Rui Li (Chemical Engineering Journal, 2025)

Pyro-phototronic effect enhanced photoelectrochemical photodetector with a graded SnO2/BFO/NiOx heterojunction for high-speed and encrypted underwater optical communication - Qidong Yin; Rui Deng; Yongfeng Li; Dayong Jiang (Chemical Engineering Journal, 2025)

A new isopropanol-intermediate mechanism for CO2-assisted propane dehydrogenation over ZIF-derived (GaCe)Ox: Toward propylene synthesis - Yun Yang; Rui Liao; Rulan Pu; Peiting Jiang; Lulu Li; Xuyu Wang; Hongbing Ji (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

How topographic and pedological factors affect vegetation responses to drought: a study from the Qinling Mountains, China - Chao Li; Zhao Jin; Chengcheng Jiang; Yanjun Shen; Rui Wang; Jianbing Peng (CATENA, 2025)

Hdac11 inhibits apoptosis in zebrafish cells under cold stress via downregulating pdcd6 through its downstream enhancer - Mingzhi Ma; Juntao Luo; Xin Li; Rui Deng; Hui Jiang; Bingshe Han; Junfang Zhang (Molecular Biology Reports, 2025)

Molecular dynamics simulation-driven focused virtual screening and experimental validation of Fisetin as an inhibitor of Helicobacter pylori HtrA protease - Li Gao; Xianqiong Jiang; Hongtao Duan; Yan Shen; Kui Gu; Kuilong Huang; Yuanqiang Wang; Mao Shu; Rui Zhang; Zhihua Lin (Molecular Diversity, 2025)

PGC1α alleviates M1 macrophage polarization through dual regulation of succinate metabolism and TRAF5 expression to mitigate TLR4/NF-κB-driven inflammatory cascades and myocardial ischemia/reperfusion injury - Jiajie Leng; Zhenrui Cao; Letai Li; Dingheng Hu; Yuxiang Luo; Bin Tu; Xiaoying Cao; Rui Tao; Yingjiu Jiang; Hongtao Tie (Inflammation Research, 2025)

Transcription factor MAZ activates the transcription of hypomethylated TYMP in ccRCC - Yihan Dong; Xinyu Liu; Jiaxin Li; Tianyu Lin; Rui Wang; Huamao Jiang; Yong Wang; Dan Yue (Functional & Integrative Genomics, 2025)

Immobilization of arsenic and antimony by silica-Fe (hydr)oxides composite: investigation of potential ecological effects on the soil microbial environment - Rui Xu; Yaxin Tian; Qian Li; Guangfei Qu; Lang Liao; Zhe Yin; Zhenguo Wu; Yuqi Han; Yan Zhang; Yongbin Yang; Dongbin Liu; Haiyan Yan; et al. (Environmental Geochemistry and Health, 2025)

Synergistic electromagnetic and chemical enhancements in Al/C3N4/Ag@C for Raman-based chlortetracycline sensing - Jingyi Sun; Lujie Li; Tingting Zhang; Na Jiang; Zishan Guo; Congying Li; Weihua Li; Xianhuai Huang; Yan Li; Rui Lu (Analytica Chimica Acta, 2025)

Simulation on the propagation characteristics of TEM pseudo-wavefield - Jun-jie Xue; Ke-rui Fan; Xin Wu; Zhi-peng Qi; Wen-han Li; Jiang-wei Cui (Applied Geophysics, 2025)

Injectable Hyaluronic Acid Hydrogels Crosslinked by Structure-engineered Aldehyde-functionalized β-Cyclodextrin Derivatives for Long-term Controlled Voriconazole Delivery - Chao Yang; Meng Xin; Yufu Jiang; Wenqian Wang; Wenhui Li; Junlin Quan; Wancong Zhou; Rui Yuan; Zhe Chen; Depeng Shi; Zhijian Ji; Xingxing Yue; et al. (AAPS PharmSciTech, 2025)

Hyperguanyes A and B, two new PPAPs from the branches and leaves of Hypericum perforatum L. with anti-cholinesterase activities - Yanan Li; Kunling Wang; Rui Liu; Jian Jiang; Donghai Zheng (Natural Product Research, 2025)

Spatial and temporal variability in molecular characteristics of dissolved organic matter in a large freshwater lake: A case from the Dongting Lake, central China - Rui Xu; Yao Du; Tianming Wu; Xinrui Jiang; Baisong Deng; Mengze Li; Yiqun Gan; Mengjie Song; Shaobo Liao; Rui Zhang; Yanxin Wang (Journal of Hydrology, 2025)

Polystyrene microplastic pollution: An abiotic factor affecting the defense of Ulmus pumila and biocontrol of Bacillus thuringiensis against Hyphantria cunea - Songfei Li; Rui Qi; Aoying Zhang; Shanchun Yan; Dun Jiang (Journal of Hazardous Materials, 2025)

Integrated assessment of chromium exposure risk from agricultural soils using chemical extraction, in vitro simulation, and mouse bioassay - Peng Xiao; Yi Zhou; Pengfei Wang; Rui Li; Shimao Xiong; Xiyan Jiang; Yunpeng Li; Yue Wu; Yuntao Yang; Xiaolin Cai; Naiyi Yin; Yanshan Cui (Journal of Hazardous Materials, 2025)

Dynamic interactions between compositional changes and color evolution in Lactobacillus fermented Lotus rhizome juice: A multivariate analysis of Browning mechanisms - Rui Huang; Huiwen Jiang; Shoulei Yan; Jie Li (Food Research International, 2025)

Na/N doped carbon dot nanozymes with enhanced peroxidase activity for antimicrobial food preservation - Dangfeng Wang; Yifan Hou; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Chemistry, 2025)

Antifungal activity and application of Neurospora sitophila Y-4 against postharvest Penicillium italicum of Citrus reticulata 'Shiyue Ju' via 3-penten-2-one - Lijun Ling; Fanjin Kong; Yijuan Jiang; Wenyue Zhang; Rongxiu Mo; Rui Yue; Yao Li; Lijun Feng; Yongpeng Zhou (Food Bioscience, 2025)

Simultaneous stabilization of high-concentration multi-heavy metal(loid)s co-contaminated soil using Fe/Mn (hydr)oxide-humic acid composites:A novel approach towards sustainable environmental remediation - Rui Xu; Chenyang Yin; Qian Li; Guangfei Qu; Lang Liao; Zhe Yin; Yan Zhang; Yongbin Yang; Tao Jiang (Environmental Research, 2025)

Laboratory characterization of VOC evaporative emissions from light-duty plug-in hybrid electric vehicles: Environmental impact comparison with conventional vehicles - Ling Li; Rui Yuan; Wei Hu; Hualong Xu; Pingjiang Lv; Qin Xu; Jun Wang; Xue Jiang; Jianxun Tan; Jianli Yin; Zhenliang Li; Dan Zhang (Environmental Pollution, 2025)

Energy flexibility at multi-building scales: A review of the dominant factors and their uncertainties - George Dawes; Tuğçin Kirant-Mitić; Zixin Jiang; Jérôme Le Dréau; Hanmin Cai; Jiyuan Cui; Jordan Townsend; Adamantios Bampoulas; Rongling Li; Rui Amaral Lopes; Bing Dong (Energy and Buildings, 2025)

Sequential targeted nanomedicine MPC treats cerebral ischemia-reperfusion injury via neuronal microenvironment reprogramming - Shuya Wang; Ruishi Li; Xiaojing Shi; Tingli Xiong; Wenxuan Zheng; Weimin Qi; Min Liu; Lin Dai; Qian Lin; Rui Huang; Wei Dai; Min Zhou; et al. (Chemical Engineering Journal, 2025)

Optimizing electromagnetic attenuation properties via controlled dielectric polarization in Zn single-atom-decorated polymer-derived SiZnCN ceramics - Hao Deng; Yang Li; Ruihua Chen; Chao Ma; Junpeng Jiang; Daoyang Han; Bingbing Fan; Hailong Wang; Rui Zhang; Gang Shao (Chemical Engineering Journal, 2025)

Calycosin ameliorates inflammation and M1 macrophage polarization via Spon2 in LPS-triggered MH-S alveolar macrophages - Gaoyan Chen; Xiaogang Li; Jingyi Zhang; Jiangli Ding; Yongchao Jiang; Rui Pan (Journal of Natural Medicines, 2025)

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

Calibration of the Edinburgh Elasto-Plastic Adhesion contact model for modelling clay-moist soil with high moisture content - Xuan Deng; Wencheng Wu; Jiawei You; Rui Jiang; Mengliang Li; Ju Li; Youfeng Tao; Hong Cheng; Wei Zhou; Fei Deng; Yong Chen; Wanjun Ren; et al. (Computers and Electronics in Agriculture, 2025)

Row-based kiwifruit counting pipeline for smartphone-captured videos using fruit tracking and detection region adaptation guided by support-post - Jiwei Zhang; Liguo Jiang; Leilei He; Zhenchao Wu; Rui Li; Jinyong Chen; Xiaoxu Sun; Yunfei Xue; Anastasia Grecheneva; Spyros Fountas; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Inverse design of three-dimensional electrocatalytic oxidation process for water purification via machine learning and DFT-based descriptors - Linjin Li; Qiyao Wang; Yaoze Wang; Guangfei Qu; Yingying Cai; Rui Xu; Ming Jiang; Nanqi Ren (Process Safety and Environmental Protection, 2025)

Monsoon and deep ocean control of organic carbon burial in the southeastern Bay of Bengal - Jingrui Li; Shengfa Liu; Hui Zhang; Xiaoming Miao; Fangliang Li; Kun Guo; Hongying Song; Rijun Hu; Rui Jiang; Somkiat Khokiattiwong; Narumol Kornkanitnan; Xuefa Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Opening of South China Sea in the Western Pacific forcing the climate cooling and lake level rise at Eocene–Oligocene transition - Jing Guo; Fujie Jiang; Guangrong Peng; Yuqi Wu; Weibing Shen; Rui Zhang; Yu An; Dapeng Jiang; Fusheng Yu; Yaqi Li; Zhifeng Yu; Jiabing Jiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Airborne bioaerosol transmission in hospital waiting corridor: Characteristic, exposure risk and evaluation of prevention strategies - Zhijian Liu; Duo Cai; Chenxing Hu; Lei Jiang; Yongxin Wang; Lina Hu; Rui Rong; Shiyue Li; Jingwei Liu; Jiajun Feng (Journal of Hazardous Materials, 2025)

Nitrogen and phosphorus addition affected soil organic carbon storage and arbuscular mycorrhizal fungi contributions - Shengchao Ma; Rui Guo; Yue Wang; Yan Yan; Qianwen Chu; Nan Cui; Yifei Zhang; Lei Zhang; Li Jiang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; et al. (Journal of Environmental Management, 2025)

Influence and mechanism of polyethylene microplastics on antibiotic resistance genes and microbial community in sludge composting process - Jie Yang; Rui Jiang; Yingchun Li; Weijian Liu; Mengmeng Wang; Peng Ren (Journal of Environmental Chemical Engineering, 2025)

Interfacial electron modulation of FeCo LDH@CoS heterojunction for efficient oxygen evolution reaction - Zhen Guan; Hengzhong Chen; Bin Chen; Lingchen Kong; Zhou Shi; Yu Zhong; Wenjie Li; Wencan Qian; Rui Zhang; Jiang Wu; Zaiguo Fu (Journal of Environmental Chemical Engineering, 2025)

Heteroatom-doped, vinegar residue-derived fluorine/chlorine Co-doped vertical graphene-supported carbon quantum dots as high-efficiency all-carbon electrodes for water electrolysis hydrogen production - Han Yin; Yang An; Chunyu Li; Yu Yan; Rui Su; Chunyang Wan; Bin Jiang; Shanshan Bai; Firdoz Shaik (Journal of Environmental Chemical Engineering, 2025)

Scale effects on buffeting response of long-span bridges - Yi Su; Mingshui Li; Jin Di; Rui Sun; Ming Li; Fengjiang Qin; Yan Jiang; Jie Wang (Engineering Structures, 2025)

Aramid nanofiber-reinforced MXene fibers for flexible supercapacitors - Yiwen Gan; Ningjing Song; Jiaxin Quan; Ting Ding; Xupu Jiang; Rui Wang; Wujun Ma; Chuntao Lan; Min Li; Meifang Zhu (Chemical Engineering Journal, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

BDNF Alleviates Noise-Induced Cochlear Synaptopathy Through Inhibition of Autophagy - Fei Wang; Qianru Yu; Yangtuo Luo; Rui Guo; Liyuan Wu; Xinyu Song; Yang Li; Shuna Li; Ke Liu; Xuejun Jiang (Molecular Neurobiology, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Desulfosporosinus sediminicola sp. nov., an acidophilic sulfate-reducing bacterium isolated from acidic sediments of a disused iron mine site - Sheng-Fang Jiang; Chu-Yi Zhang; Xuan-Wen Lao; Wei-Chao Jia; Tao-Tao Yang; Si-Yu Zhang; Ying-Ying Xie; Pei-Zhe Ye; Rui Lan; Zi-Xiang Lai; Qiang Yang; Li-Nan Huang (Antonie van Leeuwenhoek, 2025)

The phytochemical characteristics of Swertia mussotii Franch. and the potential for treating neuroinflammation in vitro through the NF-κB pathway - Yating Zheng; Jiajing Yu; Yanan Li; Hong Zhou; Guobiao Dai; Lijiao Yang; Rui Tan; Hezhong Jiang (Natural Product Research, 2025)

Anti-inflammatory and antinociceptive effects, toxicity, and phytochemical analysis of Beaumontia grandiflora Wall. - Rui Yang; Dan Teng; Ming-rui Yang; Yi-huan Li; Jian-fen Xiao; Qian-ru Zhang; Hong-ping He; Hua-yi Jiang (Natural Product Research, 2025)

YOLO-feed: An advanced lightweight network enabling real-time, high-precision detection of feed pellets on CPU devices and its applications in quantifying individual fish feed intake - Miaosheng Feng; Pengxin Jiang; Yuhang Wang; Shuimu Hu; Sijing Chen; Rui Li; Haibin Huang; Ning Li; Boyu Zhang; Qiaozhen Ke; Yu Zhang; Peng Xu (Aquaculture, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

An experimental investigation of the performance and pore structure of pervious concrete prepared from waste glass - Qiong Li; Rui Su; Xinyu Shi; Zhanying Huo; Jinlong Jiang; Hongxia Qiao (Minerals Engineering, 2025)

Extreme rainfall drives the shift in dominant water quality “Sink” from forest land to grassland in the Yellow River Basin - Jinghui Dou; Rui Xia; Xinghui Xia; Xiaohui Jiang; Kai Zhang; Yan Chen; Lina Li; Chao Yan (Journal of Hydrology, 2025)

Personnel exposure studies to multi-source diffusion of bioaerosols under biosafety laboratory - Level 2 plus operating conditions - Yongxin Wang; Zhijian Liu; Chuan Jiang; Lei Jiang; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Journal of Hazardous Materials, 2025)

Cr(VI)-bioremediation mechanism of a novel strain Bacillus sp. Cr02 with simultaneous aerobic/anaerobic reduction for Cr(VI) from soil to groundwater - Liping Liu; Rui Liu; Fang Wang; Yujun Wu; Fei Ge; Jiang Tian; Feng Li; Shengguo Xue (Journal of Hazardous Materials, 2025)

Comparative metagenomic analyses of viral genomic diversity and ecosystem functions in extremely acidic copper mine tailings - Pei-Zhe Ye; Qiang Yang; Chu-Yi Zhang; Tao-Tao Yang; Sheng-Fang Jiang; Rui Lan; Shao-Ming Gao; Li-Nan Huang (Journal of Hazardous Materials, 2025)

Unlocking the bioremediation potential of adapted Desulfovibrio desulfuricans in acidic low-temperature U-contaminated groundwater - Lei Zhou; Nan Bai; Rui Xiao; Zhendong Yang; Guoping Jiang; Huaqun Yin; Yujie Wang; Liangzhi Li; Delong Meng; Zhenghua Liu (Journal of Environmental Sciences, 2025)

The decline in desert drift potential weakens aeolian dust emission - Tong Zhang; Lianyou Liu; Peijun Shi; Gangfeng Zhang; Rui Mao; Xia Xu; Zheng Fu; Honglei Jiang; Cuicui Shi; Li Ma; Zihui Zhao; Jiaojiao Dong; et al. (Global and Planetary Change, 2025)

Quantitative non-volatile sensometabolome of Longjing tea and discrimination of taste quality by sensory analysis, large-scale quantitative metabolomics and machine learning - Xujiang Shan; Linchi Niu; Qianting Zhang; Zhizhen Fang; Yuning Feng; Rui Liang; Zhenxing Xu; Shan Zhang; Le Chen; Weidong Dai; Qinghua Zhou; Yongwen Jiang; et al. (Food Chemistry, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Root-soil-microbe interactions mediate phosphorus and iron uptake from lithium iron phosphate nanomaterials - Yaqi Jiang; Yi Sun; Changcheng An; Pingfan Zhou; Yuanbo Li; Quanlong Wang; Jason C. White; Yukui Rui; Peng Zhang (Applied Soil Ecology, 2025)

CAFM: a freeware for geochemical data processing and concentration–area fractal modeling and its application for identifying uranium anomalies of different genesis - Jun-Ting Qiu; Jiang-Kun Li; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Applied Geochemistry, 2025)

Two new diarylheptanoids from Curcuma kwangsiensis rhizomes - Shuo-Guo Li; Le Deng; Qiu-Fang Chen; Rui Yang; Cao-Min Zou; Shu-Mei Wang; Meng-Hua Wu; Jiang Meng (Natural Product Research, 2025)

Nested MPI-CWRF dynamical downscaling and future projections of summer extreme precipitation changes in China - Huan Li; Fengxue Qiao; Nan Wei; Haoran Xu; Rui Wang; Fulin Jiang; Guimin Lou; Jia Zhao; Qingyu Yang (Frontiers of Earth Science, 2025)

Improvement of nutritional value of cotton residue by solid state fermentation - Duoting Wu; Xiurong Liang; Rui Hu; Zhisheng Wang; Huawei Zou; Fali Wu; Hui Li; Yahui Jiang; Quanhui Peng; Jianxin Xiao; Hongbo Li; Zhenyong Zhou (Journal of Environmental Chemical Engineering, 2025)

Efficient in-situ transfer hydrogenation of palmitic acid into alkanes over Ni/CexZr1-xO2 solid solution catalysts in aqueous medium with methanol as the hydrogen donor - Yuhao Yan; Daxin Jiang; Rui Li; Jie Zhao; Rumin Zheng; Xianliang Song; Yulong Wu (Fuel, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

Vanadium dioxide - Perovskite tandem smart windows achieve full-spectrum modulation via plasmonic Fabry-Pérot engineering - Qiuyi Shi; Bowen Li; Yuwei Du; Sai Liu; Rui Zhang; Cancheng Jiang; Xin Li; Muhammad Fahim; Irum Firdous; Johnny C.Y. Ho; Chi Yan Tso (Chemical Engineering Journal, 2025)

Directed evolution of Escherichia coli Nissle 1917 functioning as a methylotrophic chassis - Li-Hua Liu; Zhiqian Zhang; Bo Xu; Gangzhu Yang; Hua Cui; Lijun Su; Yu Zhang; Baoqing Sun; Yi-Rui Wu; Ao Jiang (Chemical Engineering Journal, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Coupled mutual feedback and interaction mechanisms among the geological environment, ecological environment and human activities in the Qinling Mountains - Chao Li; Zhao Jin; Chengcheng Jiang; Yanjun Shen; Rui Wang; Jianbing Peng (Science China Earth Sciences, 2025)

Insight into unloading and geostress characteristics of high slopes based on valley evolution: a case study in Luding county, China - Hongfu Zhou; Shuwu Li; Fan Yang; Tian Fang; Rui Li; Jingyi Xue; Jinpeng Hu; Jiang Xing (Bulletin of Engineering Geology and the Environment, 2025)

Drivers of ecosystem service trade-off changes in different climate zones: a case study of the Sichuan–Yunnan–Loess plateau ecological shelter, China - Hao-Rui Li; Shuai Ma; Ming Zhang; Yun-Ke Yin; Hai-Bo Hu; Liang-Jie Wang; Jiang Jiang (Environment, Development and Sustainability, 2025)

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

PANoptosis: Novel insights into AFB1-Induced reproductive toxicity and the chemopreventive potential of pterostilbene - Sihong Li; Meiheng Du; Jun Jiang; Rui Li; Jiaqing Cheng; Dong Niu (Food Bioscience, 2025)

Effects of organic acids on the physico-chemical and functional characteristics of mung bean globulin amyloid fibrils - Peng Jiang; Shu Zhang; Tianxin Fu; Jingru Sun; Rui Ma; Xuejian Song; Jingjing Diao; Zhijiang Li; Changyuan Wang (Food Bioscience, 2025)

Flexural behavior of reinforced concrete beams subjected to natural corrosion in marine environment - Yang Liu; Wei-Ping Zhang; Chao Jiang; Feng Wu; Jun-Li Qiu; Rui-Lin Wang; Nai-Hao Zheng (Engineering Structures, 2025)

Decaying logs and gap positions jointly maintain the structure and function of soil invertebrate community in a subalpine forest - Yurui Jiang; Zhuang Wang; Rui Cao; Qin Wang; Weizhong Li; Wanqin Yang (Plant and Soil, 2025)

Identification and functional characterization of ssDNA in plants - Zhaoguo Li; Mahmoud Tavakoli; Rui Jiang; Lixin Zong; Wenli Zhang (Trends in Plant Science, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Ectomycorrhizal fungi and biochar promote soil recalcitrant carbon increases under arsenic stress - Xuan Zhang; Yang Liu; Xingran Mo; Zhongliang Huang; Yonghua Zhu; Hui Li; Lijuan Jiang; Zhuming Tan; Zihao Yang; Yi Zhu; Jing Huang; Baiquan Zeng; et al. (Journal of Hazardous Materials, 2025)

Assessment of fate of respiratory droplets and effectiveness of different air cleaners during outpatient consultation - Haiyang Liu; Zhijian Liu; Guangpeng Yao; Zhijian Dong; Chuan Jiang; Jingwei Liu; Rui Rong; Junzhou He; Chenxing Hu; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2025)

Evolution of and mechanisms controlling water chemistry in the Beijiang River Basin over the past four decades - Zaizhi Yang; Tao Jiang; Zuobin Liang; Xinfeng Zhao; Kun Ren; Di Tian; Lei Gao; Qirui Wu; Shaoheng Li; Rui Li; Lichun Xie; Jianyao Chen (Journal of Geochemical Exploration, 2025)

Hydrophobically modified Cu-ZnO-Al2O3 catalyst for CO2 hydrogenation to methanol - Xiuyun Jiang; Jucang Ke; Rui Li; Hao Huang; Zhihao Liu; Haozhe Feng; Qingxiang Ma; Xinhua Gao; Guangbo Liu; Xiaobo Feng; Tian-Sheng Zhao; Noritatsu Tsubaki (Journal of Environmental Chemical Engineering, 2025)

Injectable dual-network hydrogel for phototherapy and immunomodulation in the treatment of MRSA-infected and diabetic wound - Shengfei Bao; Aodi Jiang; Li Peng; Fuying Liao; Ga Liu; Li Chen; Peng Zhou; Zhen Zhu; Rui L. Reis; Subhas C. Kundu; Lian Duan; Bo Xiao; et al. (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Exogenous methyl jasmonate-mediated physiological and transcriptomic network improves thrips tolerance in alfalfa (Medicago sativa) - Shuang Shuang; Xiaowei Huo; Qi Chen; Rui Dai; Jianwei Li; Jiaxin Yan; Xiaohong Jiang; Yao Tan; Zhiqiang Zhang (Journal of Pest Science, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Ginsenoside Rf in wild ginseng adventitious roots extract inhibits melanogenesis via cAMP/PKA and NO/cGMP signalling pathways in α-melanocyte-stimulating hormone-stimulated B16F10 mouse melanoma cells and zebrafish - Hong Chen; Mengqiong Jian; Huanhuan Teng; Zhenzhuo Li; Xiaohao Xu; Xiangzhu Li; Rui Jiang; Daqing Zhao; Liwei Sun; Jianzeng Liu (Natural Product Research, 2025)

Effects of starvation-refeeding on antioxidant status, metabolic function, and adaptive response in the muscle of Cyprinus carpio - Wenrong Feng; Jianlin Li; Yuanfeng Xu; Gang Jiang; Shengyan Su; Zhihua Zhang; Rui Jia; Yongkai Tang (Aquaculture, 2025)

Multi-layer landscape design of urban spontaneous plant community: A case study in Zhengzhou, China - Wangxin Su; Zeqi Zhai; Wenhui Zhang; Rui Li; Jiayi Li; Yang Liu; Wenqian Jiang; Hong Wei; Nan Guo; Yonghua Li (Urban Forestry & Urban Greening, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Unravelling the inhibition mechanism of 1-octene-3-ol combined with 3-heptene-2-one on Aspergillus flavus and its application in the preservation of wolfberries - Lijun Ling; Rongxiu Mo; Wenyue Zhang; Yijuan Jiang; Fanjin Kong; Lijun Feng; Yao Li; Rui Yue; Yongpeng Zhou (Postharvest Biology and Technology, 2025)

Different effects of bio/non-degradable microplastics on sewage sludge compost performance: Focusing on antibiotic resistance genes, virulence factors and key metabolic functions - Xiangyu Liu; Huiyue Li; Jie Yang; Shen Yan; Yufei Zhou; Rui Jiang; Renhe Li; Mengmeng Wang; Peng Ren (Journal of Hazardous Materials, 2025)

A novel Gordonia sp. PS3 isolated from the gut of Galleria mellonella larvae: Mechanism of polystyrene biodegradation and environmental toxicological evaluation - Luhui Xu; Xuejiao An; Huoyong Jiang; Rui Pei; Zelin Li; Jiehao Wen; Wenjie Pi; Qinghua Zhang (Journal of Hazardous Materials, 2025)

Recovery of volatile ethanol gas via microalgal-bacterial consortium: Ethanol-to-acetate conversion pathway boosts lipid production - Liu-Xu Jiang; You-Wei Cui; Ya-Nan Mi; Dong-Xu Zhou; Ming-Teng Li; Rui-Chun Yang (Journal of Environmental Management, 2025)

Computer simulation analysis to improve radio frequency heating uniformity of multi-component rice samples by screening of sample structure - Yingqi Tian; Mengge Li; Longlong Jiang; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Irpex lacteus metabolites ameliorate hyperlipidemic mice via CYP7A1/HMGCR/FXR/AMPK signalling pathways and gut microbiota - Xuan Zhang; Yanye Wei; Jincheng Wu; Yue Lu; Zhenxin Zhu; Chaonan Kong; Rui Zhou; Xianke Li; Lifang Yang; Mingguo Jiang (Food Bioscience, 2025)

In-field degradation of polybutylene adipate-co-terephthalate (PBAT) films, microplastic formation, and impacts on soil health - Kai Wang; Markus Flury; Shiyan Sun; Junling Cai; Aihua Zhang; Qiang Li; Rui Jiang (Environmental Research, 2025)

In-situ preparation of CMPs based electrospun nanofibrous composite membranes for effective air filtration and oil–water separation - Yong Zhang; Anli Yi; Yongtao Ren; Cheng Niu; Jian Jiang; Zhaoqi Zhu; Rui Jiao; Hanxue Sun; An Li (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Source identification of polycyclic aromatic hydrocarbons (PAHs) in river sediments within a hilly agricultural watershed of Southwestern China: an integrated study based on Pb isotopes and PMF method - Fen Xu; Chunmei Jiang; Qiang Liu; Rui Yang; Weiwei Li; Yao Wei; Linlin Bao; Hongjin Tong (Environmental Geochemistry and Health, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Identification and fungicide sensitivity of Fusarium oxysporum, the cause of Fusarium wilt on Codonopsis pilosula in Shanxi Province (Lu Dangshen), China - Yan Wang; Dainan Hao; Haozhe Jiang; Zhaoxiong Fei; Rui Zhao; Jiaxin Gao; Guangxin Li; Chunwei Wang (Crop Protection, 2025)

Mitophagy impairment drives microglia activation and results in cognitive deficits in neonatal mice following sevoflurane exposure - Piao Zhang; Rui-Juan Cheng; Qiao-Ling Yang; Yan Gong; Yan Xu; Ling-Min Chen; Li Zhou; Chun-Ling Jiang (Toxicology Letters, 2025)

Cu-EAB zeolite catalyst: A promising candidate with excellent SO2 poisoning resistance for NH3-SCR reaction - Xiangqiong Jiang; Yu Sun; Rui Li; Dongdong Chen; Yuyan Yao; Zhifeng Zeng; Can Yang; Hongwei Chen; Hongzheng Chang; Yulong Shan; Carmine D’Agostino; Jiuxing Jiang (Journal of Hazardous Materials, 2025)

Corrigendum to “Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation” [Food Research International 203 (2025) 115792] - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

Carboxymethyl chitosan/oxidized hyaluronic acid hydrogel-encapsulated hucMSC-derived exosomes for enhanced hepatic regeneration and post-hepatectomy applications - Qiuxia Zheng; Jia Yao; Zongbin Sun; Rui Li; Yue Zhang; Pan Jiang; Ye Xie; Xiaojing Song; Hongfa Sun; Dan Zhu; Haixu Ni; Xun Li (Carbohydrate Polymers, 2025)

Clay Li isotopes reveal contrasting responses of chemical weathering intensity to hydroclimate changes in South Asia - Jingrui Li; Xuefa Shi; Shengfa Liu; Hui Zhang; Zhaowei Jing; Xiaoming Miao; Kaikai Wu; Rui Jiang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Chemical Geology, 2025)

Botryorhodine J, a new anti-MRSA depsidone isolated from endophytic fungus Alternaria alternata Pas11 - Wen-Yuan Li; Cheng-Cheng Hu; Jin-Hai Liu; Heng-Jie Wang; Ling-Pan Lu; Min Qiao; Ya-Ling Jiang; Rui Wu (Natural Product Research, 2025)

Coastal redox shifts over the past 167 years and preservation of total organic carbon and total nitrogen - Yang-Guang Gu; Hai-Song Li; Hong Su; Richard W. Jordan; Rui-Ze Liang; Shi-Jun Jiang (Marine Pollution Bulletin, 2025)

Structure, sources, functional mechanisms, and applications of bioactive glycopeptides in food: A comprehensive review - Dangfeng Wang; Benyou Zhang; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Trends in Food Science & Technology, 2025)

RNA interference-mediated silencing of GNBP2 reduces the immunity of stored pest Tribolium castaneum against bacteria - Jingxiu Bi; Xiangjun Ma; Yuying Jiang; Pingxiang Liu; Rui Gao; Tong Zhao; Xuexia Yuan; Haining Hao; Bin Li; Yutao Wang (Pesticide Biochemistry and Physiology, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Molecular networking and Paterno-Büchi reaction guided glycerides characterization and antioxidant activity assessment of Ganoderma lucidum spore oil - Qing-Xuan Ren; Rui Wang; Qin-Ru Mu; Ling Chen; Min Chen; Li-Jiang Wang; Ping Li; Hua Yang; Wen Gao (Food Chemistry, 2025)

Immune regulation differences in Large yellow croaker with varied resistance to Cryptocaryon irritans infection - Zhou Jiang; Ji Zhao; Rui Li; Qiaozhen Ke; Jiaying Wang; Yin Li; Shuimu Hu; Junjia Zeng; Fei Pu; Ning Li; Peng Xu; Tao Zhou (Fish & Shellfish Immunology, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Migration and distribution of thallium related with lead-zinc smelting enterprises from raw materials to soil: In-situ insight using diffusive gradients in thin-films - Wenhao Wang; Siwei Deng; Jiang Yu; Yi Wu; Wenjuan Feng; Qin Fan; Rui Zhou; Peirou Li; Wei Deng; Zhi Huang; Jie Yu; Weiwei Zhu (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

An eco-friendly catalytic pretreatment using recyclable CuFeO2 catalyst for enhancing the production of bio-based ethanol and jet fuel - Rui Zhang; Can Zhu; Yu Jiang; Yuming Ni; Nan Huang; Wanyun Tang; Minghui Fan; Quanxin Li (Biomass and Bioenergy, 2025)

Sequential decline in cyanobacterial, total prokaryotic, and eukaryotic responses to backward flow in a river connected to Lake Taihu - Jun Zuo; Siyu Yang; Hans-Peter Grossart; Peng Xiao; He Zhang; Rui Sun; Guoyou Li; Haoran Jiang; Qihang Zhao; Meng Jiao; Yao Cheng; Zeshuang Wang; et al. (Water Research, 2025)

Severity and risk to inhalation of pathogen-laden aerosol in large public spaces: Insights from fangcang shelter hospitals under multi-location release - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Junzhou He; Shiyue Li; Rui Rong; Zhenyu Liang; Jingwei Liu (Journal of Hazardous Materials, 2025)

Monitor and classify dough based on color image with deep learning - Bryan Gilbert Murengami; Xudong Jing; Hanhui Jiang; Xiaojuan Liu; Wulan Mao; Yuedan Li; Xueyong Chen; Shaojin Wang; Rui Li; Longsheng Fu (Journal of Food Engineering, 2025)

Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

LC-MS/MS-based quantitative method and metrological traceability technology for measuring components of animal origin in beef and lamb and their products - Yuxuan Lu; Rui Zhai; Zhanying Chu; Manman Zhu; Jingjing Li; You Jiang; Zihong Ye (Food Chemistry, 2025)

Charge density of carboxymethyl cellulose affects depletion attraction-stabilized egg yolk Pickering emulsion gels: Rheological and interfacial properties - Jingjie Hou; Yujia Liu; Zhongtao Jiang; Rui Chuang; Huajiang Zhang; Hanyu Li; Ning Xia; Yanqiu Ma; Li Zheng; Ahmed M. Rayan; Mohamed Ghamry; Dong Qin (Food Hydrocolloids, 2025)

Effects of multiple temperature variations on nitrogen removal and microbial community structure in tidal flow constructed wetlands - Xueyuan Bai; Jianwei Li; Haibo Jiang; Rui Cai; Chunguang He; Xin Ren; Bao Jiang (Environmental Research, 2025)

Graphene bilayer film responsive to ultraviolet, humidity, and temperature - Lin Wang; Tao Wang; Yalong Li; Yi Huang; Rui Li; Jing Zhang; Jie Jiang; Pei Li; Yan Fan; Liang Chen (Chemical Engineering Journal, 2025)

Revealing the blocking effect of hemicellulose on the formation of closed pores in reed-derived hard carbon for sodium-ion batteries - Zhouhao Fu; Dan Jiang; Zheng Tang; Zhi Tang; Jia Zhou; Rui Liu; Huanhuan Li; Dan Sun; Yougen Tang; Haiyan Wang (Chemical Engineering Journal, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

MiR-99a-3p downregulates TRIM21 to promote gastric cancer development - Ling He; Jiaoli Zhou; Doukun Ding; Yongjing Jiang; Rui Yang; Zhiming Li (Molecular and Cellular Biochemistry, 2025)
Gastric cancer (GC) stands as one of the most formidable malignancies worldwide. It is well-established that miRNAs play a crucial role in the initiation and progression of various human cancers. Among these, miR-99a-3p has been implicated in the pathogenesis of GC. In the context of our study, we embarked on the comprehensive examination of miR-99a-3p expression in GC cells. Additionally, we sought to establish a correlation between miR-99a-3p expression levels and the overall survival (OS) of GC patients, and our findings hinted at its potential role in predicting an unfavorable prognosis. To further investigate the functional implications of miR-99a-3p in GC, we conducted a series of cell-based experiments after successfully knocking down miR-99a-3p. These investigations uncovered a substantial inhibition of cellular events associated with tumor progression. Moreover, employing TargetScan, we identified Tripartite motif-containing protein 21 (TRIM21) as a putative target with a binding site for miR-99a-3p. Subsequent dual-luciferase reporter gene assay confirmed the direct interaction between miR-99a-3p and TRIM21. Western blot analysis validated the alteration in TRIM21 expression levels, revealing an upregulation upon miR-99a-3p knockdown. Building on these molecular findings, we extended our investigations to human GC tissues, where we observed a downregulation of TRIM21, which, notably, correlated with shorter overall survival. Lastly, to further solidify our conclusions, we conducted a series of in vitro and in vivo rescue experiments, collectively suggesting that miR-99a-3p promoted the progression of GC cells through the downregulation of TRIM21. In summary, our study comprehensively explored the role of miR-99a-3p in GC, revealing its association with unfavorable patient outcomes, functional implications in tumor progression, and a direct regulatory relationship with TRIM21. These findings collectively underscore the significance of miR-99a-3p in the pathogenesis of GC and present a potential therapeutic avenue for further investigation.

Association Between Exposure to Multiple Toxic Metals in Follicular Fluid and the Risk of PCOS Among Infertile Women: The Mediating Effect of Metabolic Markers - Xin Wang; Ying Zhang; Jie Peng; Hua Zhang; Tingting Jiang; Zhikang Zhang; Tao Yin; Xun Su; Tao Zhang; Lingchao Shen; Shitao He; Xiaolei Wang; et al. (Biological Trace Element Research, 2025)

Comparative investigation on the adsorption behavior of bromate in aqueous solutions using Zn/Ni/Al-LDH and Ni/Al-LDH: optimization, equilibrium analysis, and mechanistic insights - Yaping Qin; Huixue Ren; Shengyun Jiang; Yuxin Bi; Chuntong Li; Rui Fang (Journal of Environmental Health Science and Engineering, 2025)

Synchronous monitoring agricultural water qualities and greenhouse gas emissions based on low-cost Internet of Things and intelligent algorithms - Huazhan Zhang; Rui Ren; Xiang Gao; Housheng Wang; Wei Jiang; Xiaosan Jiang; Zhaofu Li; Jianjun Pan; Jinyang Wang; Songhan Wang; Yanfeng Ding; Yue Mu; et al. (Water Research, 2025)

Susceptibility and risk to inhalation of pathogen-laden aerosol in large public spaces: Evidence from Fangcang Shelter Hospitals under multiple ventilation rates - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Junzhou He; Shiyue Li; Rui Rong; Zhenyu Liang; Jiaqi Chu; Jingwei Liu (Sustainable Cities and Society, 2025)

Scale effects on suspended sediment and their response to extreme precipitation in karst basins - Jiang Yuan; Rui Li; Jie An; Shitian Tang; Qianying Mei; Jun Jing (Science of The Total Environment, 2025)

Microbial mechanisms of sulfate reduction for low-temperature bioremediation of acid-mined uranium sandstone groundwater - Rui Xiao; Zhenghua Liu; Min Xu; Guoping Jiang; Yang Peng; Cunzeng Li; Jie Wang; Huaqun Yin; Lechang Xu (Journal of Water Process Engineering, 2025)

Laser-induced ZnxMnOx-rGO-C@LIG materials doped with diesel distillate for Zn-ion hybrid supercapacitors - Yuxia Wang; Hu Zou; Zhong Qi; Siyu Yang; Wenlong Jiang; Rui Zhang; Zhengchun Yang; Junjun Shi; Jie He; Peng Pan; Huayi Li (Chemical Engineering Journal, 2025)

Exceptional mechanical strength and superior vibration damping characteristics in a super biomass diaphragm - Rui Yang; Anran Dong; Linghui Qi; Honggang Xu; Jinxuan Jiang; Liping Cai; Jiamin Wu; Tao Ding; Changlei Xia; Jianzhang Li (Chemical Engineering Journal, 2025)

Volatile organic compounds from Stenotrophomonas geniculata J-0 as potential biofumigants manage bulb rot caused by Fusarium oxysporum in postharvest Lanzhou lily - Lijun Ling; Rui Yue; Yuanyuan Wang; Lijun Feng; Ling Yang; Yao Li; Rongxiu Mo; Wenyue Zhang; Fanjin Kong; Yijuan Jiang; Yongpeng Zhou (World Journal of Microbiology and Biotechnology, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Prediction of available energy and amino acid digestibility in the Chinese paddy rice fed to growing pigs - Rui Li; Ganyi Feng; Qing Ouyang; Xianji Jiang; Gang Yang; Xiaojie Liu; Hui Tang; Mingzhou Tian; Qiang Xiang; Menglong Deng; Cimin Long; Ruilin Huang (Animal Feed Science and Technology, 2025)

Leaf Photosynthetic and Respiratory Thermal Acclimation in Terrestrial Plants in Response to Warming: A Global Synthesis - Ting Wu; David T. Tissue; Mingkai Jiang; Martijn Slot; Kristine Y. Crous; Junfeng Yuan; Juxiu Liu; Shaofei Jin; Chenxi Wu; Yan Deng; Chao Huang; Fuxi Shi; et al. (Global Change Biology, 2025)
Leaf photosynthesis and respiration are two of the largest carbon fluxes between the atmosphere and biosphere. Although experiments examining the warming effects on photosynthetic and respiratory thermal acclimation have been widely conducted, the sensitivity of various ecosystem and vegetation types to warming remains uncertain. Here we conducted a meta‐analysis on experimental observations of thermal acclimation worldwide. We found that the optimum temperature for photosynthetic rate ( T opt ) and the maximum rate of carboxylation of Rubisco ( T opt V) in tropical forest plants increased by 0.51°C and 2.12°C per 1°C of warming, respectively. Similarly, T opt and the optimum temperature for maximum electron transport rate for RuBP regeneration ( T opt J) in temperate forest plants increased by 0.91°C and 0.15°C per 1°C of warming, respectively. However, reduced photosynthetic rates at optimum temperature ( A opt ) were observed in tropical forest (17.2%) and grassland (16.5%) plants, indicating that they exhibited limited photosynthetic thermal acclimation to warming. Warming reduced respiration rate ( R 25 ) in boreal forest plants by 6.2%, suggesting that respiration can acclimate to warming. Photosynthesis and respiration of broadleaved deciduous trees may adapt to warming, as indicated by higher A opt (7.5%) and T opt (1.08°C per 1°C of warming), but lower R 25 (7.7%). We found limited photosynthetic thermal acclimation in needleleaved evergreen trees (−14.1%) and herbs (−16.3%), both associated with reduced A opt . Respiration of needleleaved deciduous trees acclimated to warming (reduced R 25 and temperature sensitivity of respiration (Q 10 )); however, broadleaved evergreen trees did not acclimate (increased R 25 ). Plants in grasslands and herbaceous species displayed the weakest photosynthetic acclimation to warming, primarily due to the significant reductions in A opt . Our global synthesis provides a comprehensive analysis of the divergent effects of warming on thermal acclimation across ecosystem and vegetation types, and provides a framework for modeling responses of vegetation carbon cycling to warming.

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Recycled lithium battery nanomaterials as a sustainable nanofertilizer: Reduced peanut allergenicity and improved seed quality - Yaqi Jiang; Yi Sun; Pingfan Zhou; Guikai Zhu; Qibin Wang; Yuanbo Li; Quanlong Wang; Jason C. White; Yukui Rui; Peng Zhang (Science of The Total Environment, 2024)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

Assessing the climatic niche changes and global invasion risk of Solanum elaeagnifolium in relation to human activities - Xin-Di Li; Yu Chen; Chun-Ling Zhang; Jia Wang; Xing-Jiang Song; Xian-Rui Zhang; Zhi-Hong Zhu; Gang Liu (Science of The Total Environment, 2024)

Stabilization effect of nano-SiO2@iron-phosphorus on ferrallisols, calcareous soil and organic soil heavily polluted by heavy metals: A fast reaction curing stabilization process - Zhe Yin; Qian Li; Yan Zhang; Rui Xu; Guangfei Qu; Haotian Wu; Lang Liao; Yongbin Yang; Tao Jiang (Science of The Total Environment, 2024)

Experimental and numerical simulation study on the dissipation mechanism of landslide-generated waves through multiple barrier structures - Yu-xiang Hu; Cong-jiang Li; Hai-bo Li; Da-rui Liu; Jia-wen Zhou (Ocean Engineering, 2024)

Sensitive response of erosion and weathering to the Indian Summer Monsoon changes in South Asia during Dansgaard-Oeschger oscillations - Jingrui Li; Xuefa Shi; Shengfa Liu; Fangliang Li; Xiaoming Miao; Rui Jiang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Application of metallic minerals in wastewater treatment: A review - Xuchao Sun; Yinghao Tang; Rui Li; Kaizhen Wu; Fang Shen; Shiping Zhang; Lutao Xue; Yu Jiang; Xiaoyong Wu (Journal of Water Process Engineering, 2024)

Xenobiotic metabolism activity of gut microbiota from six marine species: Combined taxonomic, metagenomic, and in vitro transformation analysis - Siqi Zhang; Rui Hou; Yuchen Wang; Qianyi Huang; Lang Lin; Hengxiang Li; Shan Liu; Zhijian Jiang; Xiaoping Huang; Xiangrong Xu (Journal of Hazardous Materials, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Thermodynamic characteristics of nitrifiers reveal the potential NOB inhibition strategies at low temperatures - Ren Li; Lifang Yu; Rui Jiang; Tian Liu; Zhuoya Li; Dangcong Peng (Journal of Cleaner Production, 2024)

Black soldier fly larvae promote the resource of cyanobacteria: Frass-mixed compost - Rui Li; YuFeng Jiang; ChangXue Wang; Kai Luo; XiaoLei Fan; TianHui Lin; RongBo Guo; ShanFei Fu (Journal of Environmental Chemical Engineering, 2024)

Study on volatile metabolites and microbial community in the fermentation process of black tea (Jiuqu hongmei tea) - Shanshan Li; Jiaxin Huang; Xueping Chen; Rui Shen; Han Jiang; Guangfa Xie; Qi Peng (International Journal of Gastronomy and Food Science, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

The effect of LuxR solo EvgA on the spoilage potential of Pseudomonas fluorescens - Dangfeng Wang; Benyou Zhang; Yunting Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Yang Jiang; Fangchao Cui; Tingting Li; Jianrong Li (Food Bioscience, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Curcumin protects porcine granulosa cells and mouse ovary against reproductive toxicity of aflatoxin B1 via PI3K/AKT signaling pathway - Sihong Li; Rui Li; Jun Jiang; Lu Liu; Xiang Ma; Tao Wang; Lili Zhao; Weifen Li; Dong Niu (Environmental Pollution, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Efficiencies and mechanisms of remediation techniques for cationic and zwitterionic per- and polyfluoroalkyl substances (PFAS) from aqueous environments: A review - Liangdi Jiang; Rui Cao; Zhouyang Huang; Jie Jin; Ziwen Du; Haixiang Li (Chemical Engineering Journal, 2024)

Enhancing hydrothermal stability of NH3-SCR reaction over Cu-SSZ-52 catalyst by increasing Si/Al ratio - Xiangqiong Jiang; Zhifeng Zeng; Dongdong Chen; Yuyan Yao; Yang Zhang; Shuangjia Wang; Rui Li; Jiuxing Jiang (Chemical Engineering Journal, 2024)

Fabrication of magnetic Cu2O nanocomposites for enhanced iodide removal: Adsorption properties, mechanism and application - Na Jiang; Juan Bao; Tingting Zhang; Lujie Li; Lan Zhang; Weihua Li; Xianhuai Huang; Jiansheng Li; Rui Lu (Chemical Engineering Journal, 2024)

Selective regulation of products for guaiacol hydrodeoxygenation by adjusting type and acidity of supports - Min Lin; Daxin Jiang; Yuhao Yan; Lulu Zhan; Xianliang Song; Rui Li; Yulong Wu (Bioresource Technology, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Ancient genomic time transect unravels the population dynamics of Neolithic middle Yellow River farmers - Shiwei Li; Rui Wang; Hao Ma; Zheng Tu; Limin Qiu; Haodong Chen; Li Jiang; Yuezu Geng; Hai Liu; Jifeng Wang; Qu Shen; Li Jin; et al. (Science Bulletin, 2024)

Dynamic nonparametric modeling of sail-assisted ship maneuvering motion based on GWO-KELM - Haoyang Zhao; Lianzhong Huang; Ranqi Ma; Kai Wang; Tiancheng Wang; Zhang Ruan; Rui Zhang; Baoshen Jiang; Xiaowu Li; Jianyi Wu (Ocean Engineering, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

A photosensitive modification of recombinant Salmonella carrying shRNA-PD-L1 promotes host immunity against poorly immunogenic tumors - Jiaying Yang; Mei Yang; Qi Wang; Qian Luo; Yingtong Wang; Jicheng Sun; Jixuan Liu; Jiasi Chen; Juanjuan Mao; Hailin Yin; Dhan V. Kalvakolanu; Baofeng Guo; et al. (Chemical Engineering Journal, 2024)

Ultrathin PVP/ZnMoO4@PE separator for high-safety sodium-ion batteries - Siya Cheng; Qingwen He; Rui Deng; Zhi Zhang; Huanyi Liao; Yifan Zheng; Zhongxi Li; Jianing Lu; Yumeng Jiang; Yihua Gao (Chemical Engineering Journal, 2024)

Multifunctional visible light photocatalytic carbon dots synergize with reactive oxygen species for anti-quorum sensing and anti-bacteria for salmon preservation - Fangchao Cui; Xin Wang; Dangfeng Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Yang Jiang; Yilin Lu; Xuepeng Li; Tingting Li; et al. (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Elevating electrochemical performance of Na4MnCr(PO4)3 cathode material for sodium ion batteries through the synergistic effect of Sc doping and RuO2/C coating - Qing Zhu; Jinxin Wu; Rui Tong; Xiuli Hu; Ningchen Tian; Botian Liu; Jiqiong Jiang; Yanwei Li; Jianwen Yang; Jianwei Zhao (Chemical Engineering Journal, 2024)

End-to-end stereo matching network with two-stage partition filtering for full-resolution depth estimation and precise localization of kiwifruit for robotic harvesting - Xudong Jing; Hanhui Jiang; Shiao Niu; Haosen Zhang; Bryan Gilbert Murengami; Zhenchao Wu; Rui Li; Chengquan Zhou; Hongbao Ye; Jinyong Chen; Yaqoob Majeed; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

Interactions between fibroblasts and monocyte-derived cells in chronic lung injuries induced by real-ambient particulate matter exposure - Youjin Zeng; Rui Zhang; Yue Jiang; Daochuan Li; Liping Chen; Guanghui Dong; Rong Zhang; Yujie Niu; Wen Chen; Shen Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Multifunctional Ni-MOF (3D) with N-rich structures for self-generated reactive oxygen species and enhanced electron transfer for synergistic degradation of organic pollutants and removal of Hg(II) - Si-Han Zhou; Rui-Dong Wang; Yun Yang; Hui-ying Li; Li-jun Luo; Feng-zhi Jiang (Journal of Cleaner Production, 2024)

Nano Fe3O4 improved the electron donating capacity of dissolved organic matter during sludge composting - Liu Chen; Zeyu Zhang; Rui Yang; Xiaojie Wang; Jieyu Yu; Hong Jiang; Wenjie Zhang; Beidou Xi; Xiaojie Sun; Ningjie Li (Journal of Environmental Management, 2024)

In situ synthesized Ag nanoparticles encapsulated inside carbonized ZIF-8 for efficient Cr(VI) reduction - Haojie Zhang; Zhuo-Rui Jiang; Yu-Xiao Zhou; Rui Chen; Hongmei Jiang; Ying Li (Journal of Environmental Chemical Engineering, 2024)

Facile synthesis of dual-functional ZIF-8-based evaporators towards high-performance in seawater desalination and uranium extraction - Zhikun Dai; Rui Gao; Qianqian Li; Mengting Qin; Jing Yang; Ran Niu; Jiang Gong (Journal of Environmental Chemical Engineering, 2024)

Self-cleaning of metal-organic framework membranes achieved by photocatalytic ZIFs for dye and antibiotic separation - Jie He; Rui Zhang; Dong Chen; Ziyin Chen; Jiacheng Jiang; Maoqing Xu; Yujie Liu; Zixi Li; Lin Peng; Yong Shu; Luming Jiang; Guixiang Zhao (Journal of Environmental Chemical Engineering, 2024)

Developing a radio frequency-hot air spouting treatment for efficient dehydration of carrot cubes: Evaluation of the heating and moisture distribution uniformity - Junjie Zheng; Xin Ye; Longlong Jiang; Xiaojiang Wang; Mengge Li; Yingqi Tian; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Enhancement of bio-jet fuel production from corncob by iron ion-catalyzed hydrogen peroxide pretreatment - Rui Zhang; Yuting He; Rui Zhu; Can Zhu; Yu Jiang; Yuming Ni; Minghui Fan; Quanxin Li (Fuel, 2024)

Relationship between microorganisms and the flavour of douchi obtained from different regions: Analysis using high-throughput sequencing and GC–MS - Rui Zhang; Jing Li; Xiaoqing Miao; Zhiyuan Song; Shan Jiang; Aidong Liu (Food Bioscience, 2024)

Colorimetric sensing based on silver nanoparticle-functionalized copper porphyrin nanozyme for glyphosate - Li-Hong Yu; Rui Jiang; Cheng-Lin Yang; Yue-Hong Pang; Xiao-Fang Shen (Food Bioscience, 2024)

Association between heatwaves and risk and economic burden of injury related hospitalizations in China - Cheng Zhao; Yushu Huang; Yibin Cheng; Rui Zhang; Yu Wang; Shilu Tong; Jiang He; Jia Guo; Fan Xia; Yonghong Li; Xiaoyuan Yao (Environmental Research, 2024)

Electric field-driven assembly of (110) oriented metal–organic framework ZIF-8 monolayer with high hydrogen selectivity - Chunxin Jin; Shuai Liu; Rui Zheng; Yanhong Li; Xiaofang Chen; Jürgen Caro; Jianwen Jiang; Aisheng Huang (Chemical Engineering Journal, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

Continuous production of pure formic acid solution from CO2 hydrogenation at room temperature via amine-functionalized PdMn nano-alloy - Xiuqin Ci; Dong Zhai; Rui Tu; Xiaoju Li; Shuchao Jiang; Xinbo Wang; Weiqiao Deng; Guoqing Ren (Chemical Engineering Journal, 2024)

Incorporating hydrogen bonding networks in microporous polymer membranes for high-flux hydrocarbon separation - Yanxiong Ren; Jingqi Fu; Rui Ding; Yunshu Li; Xu Liang; Zheyuan Guo; Jianyu Wang; Ziting Zhu; Hong Wu; Guangwei He; Zhongyi Jiang (Chemical Engineering Journal, 2024)

Multifunctional-Element doping of NASICON-Structured cathode enables High-Rate and stable sodium storage - Xi Liu; Chengcheng Zhu; Tianhe Xu; Chang Li; Xinyu Guo; Nan Jiang; Yan Chen; Yushuang Xu; Runduo Zhu; Wenxia Zou; Wenjun Deng; Rui Li (Chemical Engineering Journal, 2024)

Current status and impact of the Young Scientist Foundation of the National Natural Science Foundation on Chinese young scholars in cardiovascular research - Fei Gao; Zhenzhen Chen; Wendong Li; Hujun Jiang; Rui Wang (Science China Life Sciences, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

High-throughput proximal ground crop phenotyping systems – A comprehensive review - Z. Rui; Z. Zhang; M. Zhang; A. Azizi; C. Igathinathane; H. Cen; S. Vougioukas; H. Li; J. Zhang; Y. Jiang; X. Jiao; M. Wang; et al. (Computers and Electronics in Agriculture, 2024)

Semi-liquid metal-based highly permeable and adhesive electronic skin inspired by spider web - Rui Guo; Xiaoqing Li; Yingtong Zhou; Yuqi Zhang; Chengjie Jiang; Yang Yu; Qingting Tan; Wenbo Ding; Hongzhang Wang (Science Bulletin, 2024)

Construction of g-C3N4@Bi-MOF@BiOCl double Z-type heterojunctions for photodegradation of antibiotics under visible light irradiation: Mechanism, pathway, and toxicity assessment - Maoqin Xu; Rui Zhang; Jie He; Zixi Li; Yujie Liu; Dong Chen; Lin Peng; Yong Shu; Luming Jiang; Guixiang Zhao (Journal of Water Process Engineering, 2024)

Archean atmospheric sulfur stocked in the Cretaceous gold deposits - Yong-Wen Zhang; Hong-Rui Fan; Long Li; Qiu-Li Li; Hong-Wei Peng; Ya-Chun Cai; Peng Jiang; Kai Feng (Geochemistry, 2024)

Impact of long-term conventional and biodegradable film mulching on microplastic abundance, soil structure and organic carbon in a cotton field - Kai Wang; Wei Min; Markus Flury; Anna Gunina; Jun Lv; Qiang Li; Rui Jiang (Environmental Pollution, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Global health benefits of shipping emission reduction in early 2020 - Wenwen Sun; Wenxin Jiang; Rui Li (Atmospheric Environment, 2024)

Correction: Desmoglein-2 Affects Vascular Function in Moyamoya Disease by Interacting with MMP-9 and Influencing PI3K Signaling - Ajun Wang; Nan Li; Nan Zhang; Jian Liu; Tao Yang; Dongxue Li; Changwen Li; Rui Li; Tongcui Jiang; Chengyu Xia (Molecular Neurobiology, 2024)

Ceftriaxone Modulates Ubiquitination of α-Amino-3-Hydroxy-5-Methyl-4-Isoxazole Propionic Acid Receptors to Improve Long-Term Potentiation Impairment Induced by Exogenous β-Amyloid in a Glutamate Transporter-1 Dependent Manner - Rui Jiang; Li Li; Bu Wang; Lizhe Liu; Lirong Liu; Xiaohui Xian; Wenbin Li (Molecular Neurobiology, 2024)

Desmoglein-2 Affects Vascular Function in Moyamoya Disease by Interacting with MMP-9 and Influencing PI3K Signaling - Ajun Wang; Nan Li; Nan Zhang; Jian Liu; Tao Yang; Dongxue Li; Changwen Li; Rui Li; Tongcui Jiang; Chengyu Xia (Molecular Neurobiology, 2024)
The pathogenesis and development of Moyamoya disease are still unclear. This study aimed to investigate the effect of desmoglein-2 (DSG2) on Moyamoya disease and determine the inhibitory effect of DSG2 in vascular remodeling in Moyamoya disease. RNA sequencing, immunohistochemistry (IHC), and western blotting were used to detect the expression of DSG2 in the superficial temporal artery (STA) tissues of Moyamoya disease. The association between DSG2 and endothelial cells’ biological activities was investigated by cell counting kit-8 (CCK-8), migration assay, tube formation assay, flow cytometry with Annexin V-FITC/PI staining, and TUNEL apoptotic cell detection kit. Pathways affected by overexpression or knockdown of DSG2 were identified in endothelial cells. The expression of DSG2 in the STA tissues of Moyamoya disease was lower than that in normal controls. Overexpression of DSG2 inhibits the proliferation and migration but promotes apoptosis in endothelial cells, and low DSG2 levels result in impaired angiogenesis. In addition, there was an interaction between DSG2 and MMP-9, and DSG2 acted through the PI3K signaling in endothelial cells. Our results indicate that DSG2 affects PI3K signaling in vascular endothelial cells, and MMP-9 is involved in DSG2-mediated vascular changes in Moyamoya disease.

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

In vivo manufacture and manipulation of CAR-T cells for better druggability - Rui Hou; Xiaoxue Zhang; Xu Wang; Xuan Zhao; Sijin Li; Zhangchun Guan; Jiang Cao; Dan Liu; Junnian Zheng; Ming Shi (Cancer and Metastasis Reviews, 2024)

Green Approach for Simultaneous Quantitative Analysis of Fluoroquinolones in the Environment using Three-Dimensional Fluorescence Coupled with Second-Order Calibration Method - Yuping Yao; Liyan Song; Lingli Jiang; Mengfan Sun; Rui Li; Zhongze Zhou; Yuanna Li (Journal of Fluorescence, 2024)

Stress mitigation mechanism of rice leaf microbiota amid atmospheric deposition of heavy metals - Hanbing Gao; Zhaohui Guo; Xiao He; Jinbo Yang; Li Jiang; Aiping Yang; Xiyuan Xiao; Rui Xu (Chemosphere, 2024)

Utilizing oxygen-rich vacancies in Bi2O2CO3/ZnFe2O4 heterojunction photocatalytic materials for the efficient degradation of tetracycline hydrochloride in water - Hongqing He; Xianbin Li; Shunzhi Li; Weiwei Zhu; Rui Jiang; Zhiwei Zhai; Yang Cao (Journal of Water Process Engineering, 2024)

Spatial distribution of bioaerosols and evaluation of four ventilation method on controlling their diffusion in a typical enhanced biosafety level 2 laboratory - Zhijian Liu; Yongxin Wang; Chuan Jiang; Junzhou He; Rui Rong; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2024)

Developing a spouted bed for combined radio frequency-hot air treatments to improve the heating uniformity in high-moisture carrot cubes - Junjie Zheng; Longlong Jiang; Xin Ye; Xiaojiang Wang; Yingqi Tian; Mengge Li; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Effect of BaTiO3 as a filling material with adjustable dielectric properties on improving the radio frequency heating uniformity in red jujubes - Longlong Jiang; Junjie Zheng; Mengge Li; Yingqi Tian; Xiaojiang Wang; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Developing effective radio frequency drying processes for tiger nuts: Dynamic analysis of moisture state, dielectric properties and quality - Mengge Li; Yingqi Tian; Longlong Jiang; Juanjuan Xu; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Preparation of ternary composite film TiO2/Fe2O3/Ti3C2 for photoelectrocatalytic degradation of organic pollutants and bacterial inactivation in water - Yanping Ma; Jialin Gu; Xinshang Li; Wenquan Zhou; He Wang; Rui Zhang; Jiangang Jiang (Journal of Environmental Chemical Engineering, 2024)

Extended applications of the small-scale radio frequency system for improving the heating performance of multi-component rice - Yingqi Tian; Haibo Yu; Mengge Li; Longlong Jiang; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Regulating the electronic state of SnO2@NiFe-LDH heterojunction: Activating lattice oxygen for efficient oxygen evolution reaction - Chaojie Yin; Fanghe Zhou; Chunliang Ding; Shengde Jin; Rui Zhu; Jiang Wu; Wenhao Li; Wu Yang; Jia Lin; Xinxia Ma; Jinao Deng; Zhongjun Zhao (Fuel, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

From characteristics to practical applications of skin temperature in thermal comfort research – A comprehensive review - Jiaqi Zhao; Rui Wang; Yeyu Wu; Chaoyi Zhao; Yun Qi; Sishi Li; Haihua Jiang; Bin Cao (Building and Environment, 2024)

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Slide-controlling modes and classification system of the mélange high slopes: insight into a disaster-causing mechanism of the Jinsha River mélange belt in the eastern Tibetan Plateau - Hongfu Zhou; Meng Wang; Jingyi Xue; Rui Li; Jinpeng Hu; Jiang Xing; Tian Fang (Bulletin of Engineering Geology and the Environment, 2024)

A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

Probing rotaxane dynamics with 19F NMR/MRI: Unveiling the roles of mechanical bond and steric hindrance - Yu Li; Man Luo; Mou Jiang; Rui Zhou; Wanrong Yang; Shenhui Li; Fang Wang; Lijun Zhu; Pei He; Minghui Yang; Xin Zhou; Zhong-Xing Jiang; et al. (Analytica Chimica Acta, 2024)

Impact of high-altitude environments on the motion and settling characteristics of wet-mix shotcrete dust in tunnels - Guoliang Zhang; Zhongan Jiang; Xiaocuan Li; Ya Chen; Bin Yang; Mingli Si; Rui Feng; Ming Wang (Tunnelling and Underground Space Technology, 2024)

Recent progress and perspectives on coal dust sources, transport, hazards, and controls in underground mines - Yong Cao; Yang Xiao; Zhen-Ping Wang; Qing-Wei Li; Chi-Min Shu; Xing-Rui Jiang; Shi-Liang Wu (Process Safety and Environmental Protection, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

In situ mass spectrometry imaging reveals pesticide residues and key metabolic pathways throughout the entire cowpea growth process - Shufan Jiang; Jingling Lin; Rui Zhang; Qiong Wu; Hongxing Li; Qun Zhang; Mingyue Wang; Longjun Dai; Defang Xie; Yue Zhang; Xinzhong Zhang; Bingjun Han (Journal of Hazardous Materials, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

Oxygen vacancies-promoted removal of COS via catalytic hydrolysis over CuTiO2-δ nanoflowers - Xiaohai Zheng; Rui Huang; Bang Li; Weiping Jiang; Lijuan Shen; Ganchang Lei; Yingying Zhan; Shiping Wang; Lilong Jiang (Chemical Engineering Journal, 2024)

The Association Between the Levels of Oxidative Stress Indicators (MDA, SOD, and GSH) in Seminal Plasma and the Risk of Idiopathic Oligo-asthenotera-tozoospermia: Does Cu or Se Level Alter the Association? - Tao Yin; Xinyu Yue; Qian Li; Xinyu Zhou; Rui Dong; Jiayi Chen; Runtao Zhang; Xin Wang; Shitao He; Tingting Jiang; Fangbiao Tao; Yunxia Cao; et al. (Biological Trace Element Research, 2024)

Sustainable treatment of aquaculture water employing fungi-microalgae consortium: Nutrients removal enhancement, bacterial communities optimization, emerging contaminants elimination, and mechanism analysis - Rui Mi; Xuda Wang; Ying Dong; Shilei Li; Zelong Zhao; Xiaoyan Guan; Jingwei Jiang; Shan Gao; Zhiyu Fu; Zunchun Zhou (Science of The Total Environment, 2024)

Physiological and molecular mechanism of Populus pseudo-cathayana × Populus deltoides response to Hyphantria cunea - Yutong Ding; Jiajia Shen; Hanxi Li; Yue Sun; Tingbo Jiang; Xiangbo Kong; Rui Han; Chunli Zhao; Xinxin Zhang; Xiyang Zhao (Pesticide Biochemistry and Physiology, 2024)

Lotus pollen-derived nitrogen and phosphorus self-doped TiO2/carbon materials for photoelectrochemical application - Rui Chen; Ying-Ying Wang; Xia Jiang; Ming-Hao Ji; Ke-Xian Li; Hao-Yan Shi; Hai-Long Wang; Yan-Xin Chen; Can-Zhong Lu (Journal of Environmental Chemical Engineering, 2024)

Developing a combined rotating and air-circulating system for improving radio frequency heating uniformity and controlling Aspergillus in almond kernels - Rui Li; Yu Gao; Junjie Zheng; Mengge Li; Yujun Hao; Longlong Jiang; Shunqin Bai; Dingting Zhou; Juanjuan Xu; Xiaoxi Kou; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Effect of nano zero-valent iron on the anaerobic digestion of food waste: Performance and mechanism - Ruonan Wang; Naif Abdullah Al-Dhabi; Yufeng Jiang; Xiaofeng Dai; Rui Li; Wangwang Tang; Rongbo Guo; Shanfei Fu (Fuel, 2024)

Manipulating cationic ordering toward highly efficient and zero-thermal-quenching cyan photoluminescence - Hongzhi Zhang; Hong Li; Conglin Liu; Hongming Jiang; Junpeng Li; Yuxin Liu; Jiayi He; Rui Wang; Wanbiao Hu; Jing Zhu (Chemical Engineering Journal, 2024)

Highspeed transport pathway dominated by continuous arrangement of micron-sized hollow MOFs in MMMs to accelerate CO2 permeation - Wenji Zheng; Rui Ding; Ziheng Li; Xuehua Ruan; Yan Dai; Miao Yu; Xiangcun Li; Xiaoming Yan; Xiaobin Jiang; Xiujuan Zhang; Gaohong He (Chemical Engineering Journal, 2024)

Simultaneous biogas upgrading and single cell protein production using hydrogen oxidizing bacteria - Rui Li; YuFeng Jiang; JieHua Huang; Kai Luo; XiaoLei Fan; RongBo Guo; Tao Liu; YiFeng Zhang; ShanFei Fu (Chemical Engineering Journal, 2024)

Implantation of Adipose-Derived Mesenchymal Stromal Cells (ADSCs)-Lining Prosthetic Graft Promotes Vascular Regeneration in Monkeys and Pigs - Xiao Zuo; Pengfei Han; Ding Yuan; Ying Xiao; Yushi Huang; Rui Li; Xia Jiang; Li Feng; Yijun Li; Yaya Zhang; Ping Zhu; Hongge Wang; et al. (Tissue Engineering and Regenerative Medicine, 2024)
Background: Current replacement procedures for stenosis or occluded arteries using prosthetic grafts have serious limitations in clinical applications, particularly, endothelialization of the luminal surface is a long-standing unresolved problem. Method: We produced a cell-based hybrid vascular graft using a bioink engulfing adipose-derived mesenchymal stromal cells (ADSCs) and a 3D bioprinting process lining the ADSCs on the luminal surface of GORE-Tex grafts. The hybrid graft was implanted as an interposition conduit to replace a 3-cm-long segment of the infrarenal abdominal aorta in Rhesus monkeys. Results: Complete endothelium layer and smooth muscle layer were fully developed within 21 days post-implantation, along with normalized collagen deposition and crosslinking in the regenerated vasculature in all monkeys. The regenerated blood vessels showed normal functionality for the longest observation of more than 1650 days. The same procedure was also conducted in miniature pigs for the interposition replacement of a 10-cm-long right iliac artery and showed the same long-term effective and safe outcome. Conclusion: This cell-based vascular graft is ready to undergo clinical trials for human patients.

Primary Cutaneous Mucormycosis Caused by Mucor irregularis in a Chinese Man - Zhihua Li; Qing Jiang; Xiaohua Tao; Zhenhua Zhang; Luhuai Shi; Lifang Cheng; Pingxiu He; Xinyi Fan; Rui Xu; Yunpeng Luo; Yangmin Gao (Mycopathologia, 2024)

Clinical Characteristics and Pathogen Spectrum of Male Genital Fungal Infections in Nanchang Area, South China - Yun Jin; Yangmin Gao; Yunpeng Luo; XiaoHua Tao; Qing Jiang; Xinyi Fan; Rui Xu; Hua Qian; Xiaoguang Li; Zhijun Zhou (Mycopathologia, 2024)
The cutaneous fungal infections in male genitalia are relatively rare, and often present with various atypical clinical symptoms. It was mainly reported in a small number of case reports, while data with large number of patients were rarely reported. In this study, we reported 79 male patients with cutaneous fungal infections on scrotum or penis. The fungal infections were confirmed by microscopic examination directly and fungus culture. Clinical characteristics and predisposing factors were also collected. Of these 79 patients, 72 has lesions on scrotum, 5 on penis and 2 on both scrotum and penis. Trichophyton (T.) rubrum is the most common pathogen, found in 50 (67.6%) patients, which presented diverse clinical manifestation such as majorly erythematous, dry diffused scaly lesions without a clear border, slightly powdery and scutular scalings. Candida (C.) albicans is the secondly common pathogen, found in 21 (28.4%) patients, which also presented diverse lesions such as erythematous with dry whitish scaly lesions and erythematous erosion. The predisposing factors mainly included concomitant fungal infections on sites other than genitalia, especially inguinal region (tinea cruris), application of corticosteroid and high moisture. In conclusion, cutaneous fungal infections in male genitalia could be caused by different fungi, showed atypical or mild clinical appearances in most cases and might be a fungus reservoir, emphasizing the necessity to timely perform the fungi examinations and corresponding therapy.

Loss in the rare bacterial diversity drives the monocropping obstacle of cut chrysanthemum - Jun Li; Feng Meng; Niannian Chen; Maibo Jiang; Guixin Chu; Rui Tao (Journal of Soil Science and Plant Nutrition, 2024)

Recognition of autism spectrum disorder in children based on electroencephalogram network topology - Fali Li; Shu Zhang; Lin Jiang; Keyi Duan; Rui Feng; Yingli Zhang; Gao Zhang; Yangsong Zhang; Peiyang Li; Dezhong Yao; Jiang Xie; Wenming Xu; et al. (Cognitive Neurodynamics, 2024)

Intestinal carcinogenicity screening of environmental pollutants using organoid-based cell transformation assay - Ziwei Wang; Shen Chen; Yuzhi Guo; Rui Zhang; Qi Zhang; Xinhang Jiang; Miao Li; Yue Jiang; Lizhu Ye; Xiaoyu Guo; Chuang Li; Guangtong Zhang; et al. (Archives of Toxicology, 2024)

Combining camera trap surveys and IUCN range maps to improve knowledge of species distributions - Cheng Chen; Alys Granados; Jedediah F. Brodie; Roland Kays; T. Jonathan Davies; Runzhe Liu; Jason T. Fisher; Jorge Ahumada; William McShea; Douglas Sheil; Jayasilan Mohd‐Azlan; Bernard Agwanda; et al. (Conservation Biology, 2024)
Reliable maps of species distributions are fundamental for biodiversity research and conservation. The International Union for Conservation of Nature (IUCN) range maps are widely recognized as authoritative representations of species’ geographic limits, yet they might not always align with actual occurrence data. In recent area of habitat (AOH) maps, areas that are not habitat have been removed from IUCN ranges to reduce commission errors, but their concordance with actual species occurrence also remains untested. We tested concordance between occurrences recorded in camera trap surveys and predicted occurrences from the IUCN and AOH maps for 510 medium‐ to large‐bodied mammalian species in 80 camera trap sampling areas. Across all areas, cameras detected only 39% of species expected to occur based on IUCN ranges and AOH maps; 85% of the IUCN only mismatches occurred within 200 km of range edges. Only 4% of species occurrences were detected by cameras outside IUCN ranges. The probability of mismatches between cameras and the IUCN range was significantly higher for smaller‐bodied mammals and habitat specialists in the Neotropics and Indomalaya and in areas with shorter canopy forests. Our findings suggest that range and AOH maps rarely underrepresent areas where species occur, but they may more often overrepresent ranges by including areas where a species may be absent, particularly at range edges. We suggest that combining range maps with data from ground‐based biodiversity sensors, such as camera traps, provides a richer knowledge base for conservation mapping and planning.

Investigation of the effects and mechanisms of manganese-based NMs on rice growth - Yaqi Jiang; Yi Sun; Peng Zhang; Pingfan Zhou; Qibin Wang; Guikai Zhu; Weichen Zhao; Yuanbo Li; Quanlong Wang; Yukui Rui (Environmental Science and Pollution Research, 2024)

Morphological estimation of primary branch length of individual apple trees during the deciduous period in modern orchard based on PointNet++ - Xiaoming Sun; Leilei He; Hanhui Jiang; Rui Li; Wulan Mao; Dong Zhang; Yaqoob Majeed; Nikita Andriyanov; Vladimir Soloviev; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

H5N1 high pathogenicity avian influenza virus in migratory birds exhibiting low pathogenicity in mallards increases its risk of transmission and spread in poultry - Qiuyan Mao; Zhixin Li; Yuecheng Li; Yaxin Zhang; Shuo Liu; Xin Yin; Cheng Peng; Rui Ma; Jinping Li; Guangyu Hou; Wenming Jiang; Hualei Liu (Veterinary Microbiology, 2024)

Characteristics of second-hand exposure to aerosols from e-cigarettes: A literature review since 2010 - Tong Cui; Rui Lu; Chuan Liu; Zehong Wu; Xingtao Jiang; Yiqiao Liu; Song Pan; Yanpeng Li (Science of The Total Environment, 2024)

Records of deep-sea turbidity current activity in the Bengal Fan since the Last Glacial Maximum - Jingrui Li; Xin Shan; Xuefa Shi; Shengfa Liu; Shuqing Qiao; Hui Zhang; Kaikai Wu; Xiaoming Miao; Rui Jiang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Performance enhancement, bacterial communities optimization and emerging pollutants elimination by microalgal-bacterial consortium for treating aquaculture pond sediments - Xuda Wang; Shilei Li; Rui Mi; Ying Dong; Jingwei Jiang; Xiaoyan Guan; Xiaoyue Wang; Bo Ye; Danni Liu; Zhenjun Zhao; Xuewen Gao; Zunchun Zhou (Journal of Environmental Management, 2024)

Synthesis and characterization of a host–guest complex based on acetylated-β-cyclodextrin and its application in improving the viscosity of supercritical carbon dioxide - Wei-An Huang; Rui Su; Jing-Wen Wang; Yu Fan; Lin Jiang; Xuan Li; Jie Cao (Fuel, 2024)

Development of an analytic method for organosulfur compounds in Welsh onion and its use for nutritional quality analysis of five typical varieties in China - Pingxiang Liu; Peng Wu; Jingxiu Bi; Yuying Jiang; Rui Gao; Lei Gao; Yonghua Li; Tong Zhao; Xiao Zhang; Chao Zhang; Yutao Wang (Food Chemistry, 2024)

Synergistic enhancement of phase change materials through three-dimensional porous layered covalent triazine framework/expanded graphite composites for solar energy storage and beyond - Long Geng; Jiapeng Wang; Xulong Yang; Jiaping Jiang; Rui Li; Yabo Yan; Jiateng Zhao; Changhui Liu (Chemical Engineering Journal, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Brain-Derived Exosomal CircRNAs in Plasma Serve as Diagnostic Biomarkers for Acute Ischemic Stroke - Xinli Jiang; Rui Zhang; Geng Lu; Yu Zhou; Jianfeng Li; Xinrui Jiang; Shuangshuang Gu; Hongwei Liang; Jun Wang (Journal of Neuroimmune Pharmacology, 2024)

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

Automated segmentation of individual leafy potato stems after canopy consolidation using YOLOv8x with spatial and spectral features for UAV-based dense crop identification - Hanhui Jiang; Bryan Gilbert Murengami; Liguo Jiang; Chi Chen; Ciaran Johnson; Fernando Auat Cheein; Spyros Fountas; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

Investigation of pathogen-laden aerosol aerodynamics and ventilation rates on their long-range transmission: A study on the Fangcang shelter hospital - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Shiyue Li; Rui Rong; Zhenyu Liang; Haiyang Liu; Jingwei Liu; Tongliang Wan; Junzhou He (Journal of Cleaner Production, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Exploring debris flow deposit morphology in river valleys: Insights from physical modeling experiments - Cong-Jiang Li; Yu-Xiang Hu; Gang Fan; Qing-Yang Zhu; Da-Rui Liu; Jia-Wen Zhou (Engineering Geology, 2024)

Modeling and design of fed-batch strategies for achieving 255 g/L sugar concentration from high-solid enzymatic hydrolysis of pretreated corn stover - Haixiang Li; Rui Zhai; Xiangxue Chen; Xiaoxiao Jiang; Chen Li; Qiufeng Deng; Zhaoxian Xu; Mingjie Jin (Chemical Engineering Journal, 2024)

Losses of low‐germinating, slow‐growing species prevent grassland composition recovery from nutrient amendment - Zhongling Yang; Junyong Li; Rui Xiao; Chunhui Zhang; Xiaojun Ma; Guozhen Du; Guoyong Li; Lin Jiang (Global Change Biology, 2024)
Nutrient enrichment often alters the biomass and species composition of plant communities, but the extent to which these changes are reversible after the cessation of nutrient addition is not well‐understood. Our 22‐year experiment (15 years for nutrient addition and 7 years for recovery), conducted in an alpine meadow, showed that soil nitrogen concentration and pH recovered rapidly after cessation of nutrient addition. However, this was not accompanied by a full recovery of plant community composition. An incomplete recovery in plant diversity and a directional shift in species composition from grass dominance to forb dominance were observed 7 years after the nutrient addition ended. Strikingy, the historically dominant sedges with low germination rate and slow growth rate and nitrogen‐fixing legumes with low germination rate were unable to re‐establish after nutrient addition ceased. By contrast, rapid recovery of aboveground biomass was observed after nutrient cessation as the increase in forb biomass only partially compensated for the decline in grass biomass. These results indicate that anthropogenic nutrient input can have long‐lasting effects on the structure, but not the soil chemistry and plant biomass, of grassland communities, and that the recovery of soil chemical properties and plant biomass does not necessarily guarantee the restoration of plant community structure. These findings have important implications for the management and recovery of grassland communities, many of which are experiencing alterations in resource input.

Feedback regulation of plant secondary metabolism: Applications and challenges - Chuhan Li; Rui Jiang; Xingxing Wang; Zongyou Lv; Wankui Li; Wansheng Chen (Plant Science, 2024)

Analysis of factors affecting the performance of air gun source under shallow water conditions: Insights from the non-ideal gas air gun wavelet model - Mingxin Zhao; Jiangbo Huang; Cai Li; Jiang Li; Jiangfeng Zheng; Rui Han; Huaishan Liu (Ocean Engineering, 2024)

The transmission of isotopic signals from precipitation to groundwater and its controls: An experimental study with soil cylinders of various soil textures and burial depths in a monsoon region - Ying Jiang; Jie Li; Rui Zuo; Congjian Sun; Yuanzheng Zhai; Lijun Tian; Wei Dai; Shufang Wang; Ziqi Shang; Yulian Liu; Xuan Jiao; Yuxi Xie; et al. (Journal of Hydrology, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Arbuscular mycorrhizal fungi offset NH3 emissions in temperate meadow soil under simulated warming and nitrogen deposition - Nan Cui; Stavros Veresoglou; Yibo Tian; Rui Guo; Lei Zhang; Li Jiang; Furong Kang; Weizhe Yuan; Dan Hou; Lianxuan Shi; Jixun Guo; Mingzhou Sun; et al. (Journal of Environmental Management, 2024)

Developing a two-stage strategy in the dehydration treatment of fresh apple slices: Combined freeze and radio frequency-vacuum drying - Xiaojiang Wang; Dingting Zhou; Mengge Li; Junjie Zheng; Longlong Jiang; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Capturing spatiotemporal heterogeneity in fertilizer application for better modelling paddy water nitrogen and phosphorus pollution at regional scale - Rui Ren; Huazhan Zhang; Xiang Gao; Housheng Wang; Wei Jiang; Yuhui Wang; Xiaosan Jiang; Zhaofu Li; Haiyan Zhao; Ganghua Li; Yanfeng Ding; Yue Mu (Agriculture, Ecosystems & Environment, 2024)

Deep learning in water protection of resources, environment, and ecology: achievement and challenges - Xiaohua Fu; Jie Jiang; Xie Wu; Lei Huang; Rui Han; Kun Li; Chang Liu; Kallol Roy; Jianyu Chen; Nesma Talaat Abbas Mahmoud; Zhenxing Wang (Environmental Science and Pollution Research, 2024)

Improved binocular localization of kiwifruit in orchard based on fruit and calyx detection using YOLOv5x for robotic picking - Changqing Gao; Hanhui Jiang; Xiaojuan Liu; Haihong Li; Zhenchao Wu; Xiaoming Sun; Leilei He; Wulan Mao; Yaqoob Majeed; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

An AI-powered approach to improving tunnel blast performance considering geological conditions - Yaosheng Liu; Ang Li; Feng Dai; Ruochen Jiang; Yi Liu; Rui Chen (Tunnelling and Underground Space Technology, 2024)

Co-application of concentrated biogas slurry and pyroligneous liquor mitigates ammonia emission and sustainably releases ammonium from paddy soil - Zichuan Li; Rui Zhang; Jianfeng Jiang; Yanjun Chai; Haijun Yang; Yutong Zong; Wenbin Tong; Mengting Yuan; Ronghui Li; Lanting Wang; Shengdao Shan; Ming Hung Wong (Science of The Total Environment, 2024)

Structurally diverse rearranged sesquiterpenoids, including a pair of rare tautomers, from the aerial parts of Daphne penicillata - Peng Zhao; Ben-Song Xin; Li Ye; Zhen-Tao Ma; Guo-Dong Yao; Rui Shi; Xia-Hong He; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Suspended sediment dynamics and linking with watershed surface characteristics in a karst region - Linlv Xiao; Rui Li; Jun Jing; Jiang Yuan; Zhengyi Tang (Journal of Hydrology, 2024)

Change of soil bacterial communities in chemically stabilized chromium contaminated soils in an accelerated aging experiment - Linying Yao; Yuning He; Peng Zhao; Zhihao Xie; Longfei Jiang; Danni Li; Yueqiao Liu; Rui Ma; Jianli Jia; Dayi Zhang (Journal of Environmental Chemical Engineering, 2024)

Modulating surface zinc species via facet engineering for efficient electroreduction of CO2 to CO - Junjie Wang; Zhaozhao Zhu; Yingxi Lin; Xueqiang Qi; Zhao Li; Jinxia Jiang; Xiaobin Niu; Jun Song Chen; Rui Wu (Chemical Engineering Journal, 2024)

Constructing novel deep eutectic composites based on hydrogen bond network as anode material for lithium-ion batteries - Yiting Wang; Yifei Li; Jiali Chai; Qingmeng Li; Jiakai Du; Yichuan Rui; Bohejin Tang; Lei Jiang (Chemical Engineering Journal, 2024)

Temperature–Controlled hydrothermal hydrogenation of palmitic acid to alkanol or alkanes over Co@CN–x catalysts derived from ZIF–67 - Min Lin; Daxin Jiang; Yuhao Yan; Xiaoxian Li; Lulu zhan; Xianliang Song; Rui Li; Yulong Wu (Chemical Engineering Journal, 2024)

In situ bioprinting of double network anti-digestive xanthan gum derived hydrogel scaffolds for the treatment of enterocutaneous fistulas - Kang Chen; Jinjian Huang; Ze Li; Jinpeng Zhang; Sicheng Li; Canwen Chen; Ye Liu; Guiwen Qu; Yitian Teng; Rui Ma; Zongan Li; Yungang Jiang; et al. (Carbohydrate Polymers, 2024)

Investigating the Immunogenic Cell Death-Dependent Subtypes and Prognostic Signature of Triple-Negative Breast Cancer - Youyang Shi; Yuanyuan Wu; Feifei Li; Kexin Jiang; Xiaofang Fang; Yu Wang; Xiaoyun Song; Rui Wang; Lixin Chen; Jinzhou Zheng; Chunyu Wu; Yuenong Qin; et al. (Phenomics, 2024)

GABRP Promotes the Metastasis of Pancreatic Cancer by Activation of the MEK/ERK Signaling Pathway - Yong Meng; Rui Li; Shuaiming Geng; Wenhao Chen; Weirong Jiang; Zhiwen Li; Ji Hao; Zhen Xu (Biochemical Genetics, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Prediction interaction responses between railway subgrade and shield tunnelling using machine learning with sparrow search algorithm - Xiang Liu; Kuichen Li; Annan Jiang; Qian Fang; Rui Zhang (Transportation Geotechnics, 2024)

The decomposition of algae has a greater impact on heavy metal transformation in freshwater lake sediments than that of macrophytes - Si-Min Xue; Shu-Qi Jiang; Rui-Ze Li; Yi-Ying Jiao; Qun Kang; Li-Ya Zhao; Zhao-hua Li; Mo Chen (Science of The Total Environment, 2024)

Meteoric diagenesis influenced by East Asian Summer Monsoon: A case study from the Pleistocene carbonate succession, Xisha Islands, South China Sea - Lü Wu; Rui Wang; Kefu Yu; Min Ren; Simone Booker; Ruoxia Shen; Wei Jiang; Shendong Xu; Tianlai Fan; Songye Wu; Qiushuang Qin; Xingchi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Performance analysis of the comprehensive energy system based on active energy storage-discharge technology under time-sharing electricity price operation strategy - Dong Zhang; Yuzhan Jiang; Shaohua Wang; Haoran Li; Jianhua Bai; Rui Zhang; Zhoujian An (Journal of Cleaner Production, 2024)

A review of the strategy to promote microalgae value in CO2 conversion-lipid enrichment-biodiesel production - Huan Liu; Tian-Ji Liu; Hua-Wei Guo; Ya-Jun Wang; Rui Ji; Le-Le Kang; Yi-Tong Wang; Xuan Guo; Jun-Guo Li; Li-Qun Jiang; Zhen Fang (Journal of Cleaner Production, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Harnessing synergy: Integrating agricultural waste and nanomaterials for enhanced sustainability - Yuying Tang; Weichen Zhao; Li Gao; Guikai Zhu; Yaqi Jiang; Yukui Rui; Peng Zhang (Environmental Pollution, 2024)

Plasma membrane-localized hexose transporter OsSWEET1b, affects sugar metabolism and leaf senescence - Qiang Zhang; Changzhao Chen; Rui Guo; Xiaofang Zhu; Xinyu Tao; Mengxing He; Zhiwen Li; Lan Shen; Qing Li; Deyong Ren; Jiang Hu; Li Zhu; et al. (Plant Cell Reports, 2024)

Recent advances in the development of bitter gourd seed oil: from chemical composition to potential applications - Huiling Wang; Xiaoyan Shuai; Shuxin Ye; Rui Zhang; Muci Wu; Sijia Jiang; Yubao Li; Dong Wu; Jingren He (Critical Reviews in Food Science and Nutrition, 2023)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

Preparation of curcumin-chitosan composite film with high antioxidant and antibacterial capacity: Improving the solubility of curcumin by encapsulation of biopolymers - Han Li; Yanling Jiang; Jisheng Yang; Rui Pang; Yanan Chen; Liuting Mo; Qiong Jiang; Zhiyong Qin (Food Hydrocolloids, 2023)

Cyanidin-3-O-glucoside from blueberry anthocyanin extracts protects ARPE-19 cells against high glucose damage via REDD1/GSK3β pathway - Rui Li; Zhan Ye; Yong-jiang Xu; Yuanfa Liu (Food Bioscience, 2023)

Volatile organic compounds of Bacillus spp. as an emerging antifungal resource play a significant role in fruit postharvest disease control - Lijun Ling; Yao Li; Kunling Jiang; Yuanyuan Wang; Hong Luo; Wenting Cheng; Mingmei Pang; Lijun Feng; Rui Yue; Yongpeng Zhou (Food Bioscience, 2023)

Genomic and biogenic amine-reducing characterization of Lactiplantibacillus planatraum JB1 isolated from fermented dry sausage - Shan Qin; Xian Ming Zeng; Mei Jiang; Xin Rui; Wei Li; Ming Sheng Dong; Xiao Hong Chen; Qiu Qin Zhang (Food Control, 2023)

Characteristics of dissolved organic matter in point-source wastewaters at a petrochemical plant: Molecular constituents and contributions to the influent of wastewater treatment plant - Yue Kou; Baiyu Yang; Juntao Jiang; He Sun; Rui Zhang; Zhuoyu Li; Qinghong Wang; Quan Shi; Chunmao Chen (Environmental Research, 2023)

17β-Estradiol Mediates Staphylococcus aureus Adhesion in Vaginal Epithelial Cells via Estrogen Receptor α-Associated Signaling Pathway - Lina Yan; Can Rui; Bin Zhuang; Xia Liu; Ting Luan; Lisha Jiang; Zhiyong Dong; Qing Wang; Aiwen Wu; Ping Li; Xinyan Wang; Xin Zeng (Current Microbiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

PM1 exposure and spatial transmission of nicotine from the simulated second-hand vapor of pod-based electronic cigarettes - Tong Cui; Rui Lu; Qianyun Liu; Xingtao Jiang; Yanpeng Li; Song Pan (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Plant and animal positive-sense single-stranded RNA viruses encode small proteins important for viral infection in their negative-sense strand - Pan Gong; Qingtang Shen; Mingzhen Zhang; Rui Qiao; Jing Jiang; Lili Su; Siwen Zhao; Shuai Fu; Yu Ma; Linhao Ge; Yaqin Wang; Rosa Lozano-Durán; et al. (Molecular Plant, 2023)

Novel Fe trihalides solid molten salt-FeX3 (X = F, Cl, Br) via one-step method with low temperature as anodes of lithium-ion batteries - Yifei Li; Yiting Wang; Zhiyuan Chen; Qingmeng Li; Jiakai Du; Jiali Chai; Longzhen Wang; Yichuan Rui; Lei Jiang; Bohejin Tang (Chemical Engineering Journal, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Insights into influence of CeO2 crystal structure effects on hydrothermal hydrogenation for palmitic acid over Ni/CeO2 catalysts - Min Lin; Yuhao Yan; Daxin Jiang; Xiaoxian Li; Rui Li; Yulong Wu (Chemical Engineering Journal, 2023)

Comprehensive properties of non-penetrating and penetrating deep convection precipitation in summer over the Tibetan Plateau derived from GPM observations - Rui Wang; Zhongshan Jiang; Fengjiao Chen; Wenshou Tian; Liangliang Li; Hongying Tian; Jiali Luo (Atmospheric Research, 2023)

Human amnion-derived mesenchymal stem cells improve subclinical hypothyroidism by immunocompetence mediating apoptosis inhibition on thyroid cells in aged mice - Chuyu Li; Qiang Rui; Xiaohan Dong; Song Ning; Jing Zhou; Huimin Wu; Chunyan Jiang; Yugui Cui; Jiayin Liu; Jun Jiang; Lianju Qin (Cell and Tissue Research, 2023)
Subclinical hypothyroidism (SCH) affects 10% of the global population, which is most prevalent in women and the elderly. However, it remains debatable whether the elderly with subclinical hypothyroidism needs thyroxine supplement. Human amnion-derived mesenchymal stem cells (hAMSCs) could play important roles in autoimmune diseases, suggesting that hAMSC be a candidate to regulate the thyroid function of female age-related subclinical hypothyroidism. Herein, we established the model of SCH in the aged female mice. This study was designed to investigate whether human amnion-derived mesenchymal stem cells (hAMSC) could effect on immune regulation, apoptosis inhibition of thyroid cells, thyroid function, blood lipid levels, and heart function. In addition, qualified hAMSCs were intravenously injected into aged female SCH mice via the tail vein on day 0 and day 10. The levels of thyroid hormone and blood lipids as well as cardiac function, serum immunological indexes, and apoptosis of thyroid cells were then analyzed on day 5, 10, 15, and 20; meanwhile, the quantity of Th1, Th2, Th17, and Treg immune cells in peripheral blood was evaluated before and on day 20 post-injection. Our study demonstrated that after hAMSC transplantation, the thyroid functions, blood lipid levels, and heart function indexes of age-related SCH (AR-SCH) mice were significantly improved. Consistent with this, Th1 and Treg cells increased significantly, while Th2 and Th17 cells decreased in peripheral blood. Apoptosis was also suppressed in the thyroid cells. In summary, hAMSC delivery can potentially be a safe and effective therapy for treating SCH in the elderly, improving related complications by immunomodulatory and apoptosis inhibition.

Coarse woody debris and litter layer exert differential roles in nursing soil fungal communities across a subalpine forest successional series - Zhihui Wang; Fei Li; Jianfeng Hou; Xuqing Li; Rui Cao; Yurui Jiang; Yuchen Lu; Shuning Ma; Wanqin Yang (Acta Oecologica, 2023)

Twice matched fruit counting system: An automatic fruit counting pipeline in modern apple orchard using mutual and secondary matches - Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Fangfang Gao; Rui Li; Longsheng Fu; Dong Zhang; Spyros Fountas (Biosystems Engineering, 2023)

Recent innovations in microplastics and nanoplastics removal by coagulation technique: Implementations, knowledge gaps and prospects - Imran Ali; Xiao Tan; Yue Xie; Changsheng Peng; Juying Li; Iffat Naz; Zhipeng Duan; Peng Wan; Jiang Huang; Jia Liang; Zhu Rui; Yinlan Ruan (Water Research, 2023)

An integrative analysis of lipidomics and transcriptomics in various mouse brain regions in response to real-ambient PM2.5 exposure - Shuangjian Qin; Huixian Zeng; Qizhen Wu; Qingqing Li; Mohammed Zeeshan; Lizhu Ye; Yue Jiang; Rui Zhang; Xinhang Jiang; Miao Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

A new norditerpenoid and other components from Ajuga macrosperma and their bioactivity - Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Hong-Ping He; Rui Yang; Hua-Yi Jiang (Phytochemistry Letters, 2023)

Membrane flux response technology for early warning of initial surface scaling in membrane distillation - Zhijie Yuan; Rui Zhao; Guoxin Sun; Peiyu Li; Shaohua Yin; Guoli Zhou; Gaohong He; Xiaobin Jiang (Journal of Water Process Engineering, 2023)

Symbiotic hemolymph bacteria reduce hexavalent chromium to protect the host from chromium toxicity in Procambarus clarkii - Cheng-Ming Yin; Rui-Geng Niu; Hui Wang; Xian-Yao Li; Qi-Fan Zeng; Jiang-Feng Lan (Journal of Hazardous Materials, 2023)

Nano-agriculture and nitrogen cycling: Opportunities and challenges for sustainable farming - Quanlong Wang; Li Gao; Yuanbo Li; Noman Shakoor; Yi Sun; Yaqi Jiang; Guikai Zhu; Fayuan Wang; Yunze Shen; Yukui Rui; Peng Zhang (Journal of Cleaner Production, 2023)

Characterization of different grades of Jiuqu hongmei tea based on flavor profiles using HS-SPME-GC-MS combined with E-nose and E-tongue - Qi Peng; Shanshan Li; Huajun Zheng; Kai Meng; Xi Jiang; Rui Shen; Jingrun Xue; Guangfa Xie (Food Research International, 2023)

Seismic and hydrological triggers for a complex cascading geohazard of the Tianmo Gully in the southeastern Tibetan Plateau - Rui Guo; Liming Jiang; Zhida Xu; Chao Li; Ronggang Huang; Zhiwei Zhou; Tao Li; Yi Liu; Hansheng Wang; Xuanmei Fan (Engineering Geology, 2023)

Understanding acid hydrolysis of corn stover during densification pretreatment for quantitative predictions of enzymatic hydrolysis efficiency using modified pretreatment severity factor - Xiaoxiao Jiang; Rui Zhai; Haixiang Li; Chen Li; Qiufeng Deng; Mingjie Jin (Bioresource Technology, 2023)

Realgar-Induced Neurotoxicity: Crosstalk Between the Autophagic Flux and the p62-NRF2 Feedback Loop Mediates p62 Accumulation to Promote Apoptosis - Rui Feng; Jieyu Liu; Zhao Yang; Tiantian Yao; Ping Ye; Xiuhan Li; Jiaxin Zhang; Hong Jiang (Molecular Neurobiology, 2023)

From anaerobic digestion to single cell protein synthesis: A promising route beyond biogas utilization - Rui Li; XiaoLei Fan; YuFeng Jiang; RuoNan Wang; RongBo Guo; Yifeng Zhang; ShanFei Fu (Water Research, 2023)

Structure, rheology, and antifreeze property of the exopolysaccharide from Naematelia aurantialba through basidiospore fermentation - Tao Sun; Xiaoyi Xu; Yuhang Ma; Hao jiang; Kai Yang; Rui Wang; Yian Gu; Sha Li; Yibin Qiu; Dafeng Sun; Hong Xu; Peng Lei (Food Hydrocolloids, 2023)

A reliable Bayesian neural network for the prediction of reservoir thickness with quantified uncertainty - Li-Li Bao; Jiang-She Zhang; Chun-Xia Zhang; Rui Guo; Xiao-Li Wei; Zi-Lu Jiang (Computers & Geosciences, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Remarkable bioactivity, bio-tribological, antibacterial, and anti-corrosion properties in a Ti-6Al-4V-xCu alloy by laser powder bed fusion for superior biomedical implant applications - Jiang Ju; Rui Zan; Zhao Shen; Chenchen Wang; Peng Peng; Jun Wang; Baode Sun; Bo Xiao; Qian Li; Shaofei Liu; Tao Yang (Chemical Engineering Journal, 2023)

NDMFCS: An automatic fruit counting system in modern apple orchard using abatement of abnormal fruit detection - Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Wulan Mao; Rui Li; Nikita Andriyanov; Vladimir Soloviev; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Emission factors of ozone-depleting chloromethanes during production processes based on field measurements surrounding a typical chloromethane plant in China - Bowei Li; Xingchen Zhao; Xinhe Li; Xiaoyi Hu; Liting Hu; Di Chen; Minde An; Yang Yang; Rui Feng; Liya Guo; Pengnan Jiang; Bo Yao; et al. (Journal of Cleaner Production, 2023)

Exploratory quantification of 3D spatial competition in ecotone of trees and bamboos using terrestrial laser scanner - Jiayuan Lin; Yangyu Chen; Rui Jiang; Tianxi Li (Forest Ecology and Management, 2023)

Assessing the occurrence and sources of synthetic additive pollutants in lake sediments using fecal and sewage markers - Rui Du; Xiaoxia Feng; Pu Wang; Ruiqiang Yang; Gang Li; Jianjie Fu; Yong Liang; Ting Ruan; Guibin Jiang (Environmental Pollution, 2023)

Norethindrone suppress the germ cell development via androgen receptor resulting in male bias - Xiao-Bing Long; Wen-Jun Shi; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Fluorescence enhancement of surface plasmon coupled emission by Au nanobipyramids and its modulation effect on multi-wavelength radiation - Kai-Xin Xie; Rui-Ping Huo; Xiu-Li Song; Qiao-Ling Liu; Yue Jiang; Yu-Han Li; Lu-Lu Dong; Jia-Xin Cheng (Analytica Chimica Acta, 2023)

High prevalence of vitamin D deficiency in Asia: A systematic review and meta-analysis - Zhiwei Jiang; Rui Pu; Na Li; Chaozhen Chen; Jialu Li; Wei Dai; Yuchen Wang; Jinxing Hu; Danji Zhu; Qiong Yu; Yuan Shi; Guoli Yang (Critical Reviews in Food Science and Nutrition, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Characteristics, sources and health risks of organotin compounds in marine organisms from the seas adjacent to the eastern ports of China - Sheng-Nan Shu; Rui-Tong Jiang; Jie Yin; Qian Wang; Lei Su; Nicholas J. Craig; Juan-Ying Li (Regional Studies in Marine Science, 2023)

Paleozoic remelting of carbonatite in Bayan Obo (China): Further insights into the formation of a giant REE deposit - Hai-Dong She; Hong-Rui Fan; M. Santosh; Xiao-Chun Li; Kui-Feng Yang; Qi-Wei Wang; Wei Wei; Yan-Jiang Liu; Shang Liu; Shuang-Liang Liu (Gondwana Research, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

Structure of a novel Co-based heterogeneous catalyst via Mn3(PO4)2 as a carrier to efficiently activate peroxymonosulfate for improving degradation of sulfonamides - Yuxin Li; Zhuo-Rui Jiang; Xiaoli Yang; Yeqing Lan; Jing Guo (Chemosphere, 2023)

Thin wire segmentation and reconstruction based on a novel image overlap-partitioning and stitching algorithm in apple fruiting wall architecture for robotic picking - Hanhui Jiang; Xiaoming Sun; Wentai Fang; Longsheng Fu; Rui Li; Fernando Auat Cheein; Yaqoob Majeed (Computers and Electronics in Agriculture, 2023)

Phenotyping of individual apple tree in modern orchard with novel smartphone-based heterogeneous binocular vision and YOLOv5s - Guanao Zhao; Ruizhe Yang; Xudong Jing; Haosen Zhang; Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Rui Li; Xiaofeng Wei; Spyros Fountas; Huijun Zhang; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Rainstorm sediment events in heterogeneous karst small watersheds: Process characteristics, prediction modeling and management enlightenment - Jun Jing; Jiang Yuan; Rui Li; Zaike Gu; Li Qin; Jiayong Gao; Linlv Xiao; Zhenyi Tang; Ling Xiong (Science of The Total Environment, 2023)

Chemical constituents from Ajuga macrosperma Wall. ex Benth. (Lamiaceae) and their chemotaxonomic significance - Hua-Yi Jiang; Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Ming-Ming Li; Rui Yang; Hong-Ping He (Biochemical Systematics and Ecology, 2023)

Correction to: Inhibition of mGluR5 alters BDNF/TrkB and GLT‑1 expression in the prefrontal cortex and hippocampus and ameliorates PTSD‑like behavior in rats - Shuyue Cheng; Jingjing Xu; Wei Wang; Rui Wang; Haonan Li; Zhijun Jiang; Dexiang Liu; Fang Pan (Psychopharmacology, 2023)

Hippocampus: Molecular, Cellular, and Circuit Features in Anxiety - Hu-Jiang Shi; Shuang Wang; Xin-Ping Wang; Rui-Xin Zhang; Li-Juan Zhu (Neuroscience Bulletin, 2023)

Correction: Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

Short-term effect of apparent temperature on daily hospitalizations for osteoporotic fractures in Beijing, China: A retrospective observational study - Shuai Lu; Xuejiao Liu; Yanlin Niu; Feng Li; Maoqi Gong; Yejun Zha; Qingchen Chao; Bo Lu; Baichao Zhang; Ning Li; Jia Chen; Qiyong Liu; et al. (Science of The Total Environment, 2023)

Examining moisture contribution for precipitation in response to climate change and anthropogenic factors in Hengduan Mountain Region, China - Xingxing Zhang; Zhaofei Liu; Yubo Liu; Liguang Jiang; Rui wang; Hou Jiang; Jing Li; Qiuhong Tang; Zhijun Yao (Journal of Hydrology, 2023)

Exposure to real-ambient particulate matter induced vascular hypertrophy through activation of PDGFRβ - Hongxu Bao; Benying Li; Qing You; Xinyu Dun; Zhen Zhang; Yanan Liang; Yahui Li; Qixiao Jiang; Rong Zhang; Rui Chen; Wen Chen; Yuxin Zheng; et al. (Journal of Hazardous Materials, 2023)

Abiotic transformation of synthetic progestins in representative soil mineral suspensions - Xingjian Yang; Rui Wang; Zhili He; Xiong Dai; Xiuping Jiang; He Liu; Yongtao Li (Journal of Environmental Sciences, 2023)

Heavy metals in riverine/estuarine sediments from an aquaculture wetland in metropolitan areas, China: Characterization, bioavailability and probabilistic ecological risk - Hai-Song Li; Yang-Guang Gu; Rui-Ze Liang; Ya-Su Wang; Richard W. Jordan; Liang-Gen Wang; Shi-Jun Jiang (Environmental Pollution, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A novel pollination robot for kiwifruit flower based on preferential flowers selection and precisely target - Changqing Gao; Leilei He; Wentai Fang; Zhenchao Wu; Hanhui Jiang; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

NAT10 accelerates pulmonary fibrosis through N4-acetylated TGFB1-initiated epithelial-to-mesenchymal transition upon ambient fine particulate matter exposure - Shenshen Wu; Lijia Yin; Ke Han; Bo Jiang; Qingtao Meng; Michael Aschner; Xiaobo Li; Rui Chen (Environmental Pollution, 2023)

The role of intercellular junction proteins in the penetration resistance of Drosophila larvae to avermectin - Li-Ping Chen; Han-Qing Jiang; Liang Luo; Jun Qiu; Xue-Jie Xing; Rui-Yan Hou; Yi-Jun Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Comparison and Investigation of Exosomes from Human Amniotic Fluid Stem Cells and Human Breast Milk in Alleviating Neonatal Necrotizing Enterocolitis - Xiaohan Hu; Rui Zhang; Hansi Liang; Jingnan An; Yuan Yang; Jie Huo; Zhenjiang Chen; Wei Quan; Lu Jiang; Cancan Li; Jian Li; Fang Li; et al. (Stem Cell Reviews and Reports, 2023)
In view of the devastating impact of neonatal necrotizing enterocolitis (NEC) on newborns, the research on its intervention is particularly important. Although exosomes from human amniotic fluid stem cells (AFSC) and human breast milk (HBM) can protect against NEC, their mechanisms remain unclear. Here, we intend to compare the intervention effects of two types of exosomes on NEC mouse model and reveal their respective regulatory mechanisms. In general, both AFSC-derived exosomes (AFSC-exos) and HBM-derived exosomes (HBM- exos) can alleviate NEC- associated intestinal injury, significantly reduce NEC score, and reduce systemic and ileal inflammation and NEC related brain injury during experimental NEC. However, the mode and mechanism of action of the two sources of exosomes were not identical. In vivo, the number of ileal crypts was more significantly restored after HBM-exos intervention than AFSC-exos, and in vitro, HBM-exos preferentially inhibited the inflammatory response of intestinal epithelial cells (IECs), whereas AFSC-exos preferentially regulated the migration of IECs. Mechanistically, GO and KEGG analyses revealed the different therapeutic mechanisms of AFSC-exos and HBM-exos in NEC. Taken together, our results illustrate that AFSC-exos and HBM-exos reduce the severity of experimental NEC and intestinal damage through different mechanisms, supporting the potential of cell-free or breast milk free exosome therapy for NEC. Graphical Abstract

Inhibition of mGluR5 alters BDNF/TrkB and GLT-1 expression in the prefrontal cortex and hippocampus and ameliorates PTSD-like behavior in rats - Shuyue Cheng; Jingjing Xu; Wei Wang; Rui Wang; Haonan Li; Zhijun Jiang; Dexiang Liu; Fang Pan (Psychopharmacology, 2023)

Determination and prediction of digestible energy, metabolizable energy, and standardized ileal digestibility of amino acids in barley for growing pig - Rui Li; Mingzhou Tian; Ganyi Feng; Gaifeng Hou; Xianji Jiang; Gang Yang; Qiang Xiang; Xiaojie Liu; Cimi Long; Ruilin Huang; Yulong Yin (Animal Feed Science and Technology, 2023)

Morphological alterations in C57BL/6 mouse intestinal organoids as a tool for predicting chemical-induced toxicity - Ziwei Wang; Shen Chen; Yaqin Pang; Lizhu Ye; Qi Zhang; Xinhang Jiang; Rui Zhang; Miao Li; Zhanyu Guo; Yue Jiang; Daochuan Li; Xiumei Xing; et al. (Archives of Toxicology, 2023)

Quality prediction of tractor rotary tillage based on BiConvLSTM with self-attention - Ruo-chen Li; Chang-kai Wen; Shu-yan Li; Rui Li; Hong-yu Pu; Yu Jiang; Zheng-he Song (Computers and Electronics in Agriculture, 2023)

Corrigendum to “Limited hydrolysis of glycosylated whey protein isolate ameliorates the oxidative and physical stabilities of conjugated linoleic acid oil-in-water emulsions” [Food Chem. 362 (2021)130212] - Meng Li; Rui Yu; Runxiao Fu; Yanting He; Zhanmei Jiang; Juncai Hou (Food Chemistry, 2023)

Iron-based nanomaterials reduce cadmium toxicity in rice (Oryza sativa L.) by modulating phytohormones, phytochelatin, cadmium transport genes and iron plaque formation - Pingfan Zhou; Peng Zhang; Mengke He; Yu Cao; Muhammad Adeel; Noman Shakoor; Yaqi Jiang; Weichen Zhao; Yuanbo Li; Mingshu Li; Imran Azeem; Like Jia; et al. (Environmental Pollution, 2023)

Detecting ionizing radiation dose using composite hydrogel-based sensors - Li Jiang; Chengfang Zhang; Xinyue Xu; Rui Hu; Ping Zhang; Rensheng Wang; Xinjian Chen; Liang Hu (Chemical Engineering Journal, 2023)

Gonad development and recruitment pattern of the oysters Crassostrea ariakensis and Crassostrea sikamea in a subtropical bay in China - Wei Jiang; Wen-Jing Shi; Nan-Nan Li; Wen-Kao Zhang; Li-Zhi Chen; Qi Liu; Chun-Yu Ye; Rui-Liang Fan; Wei-Min Quan (Regional Studies in Marine Science, 2023)

Guide isolation of guaiane-type sesquiterpenoids from Daphne tangutica maxim. And their anti-inflammatory activities - Rui Guo; Zhi-Kang Duan; Qian Li; Guo-Dong Yao; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

In situ preparation of a multifunctional adsorbent by optimizing the Fe2+/Fe3+/Mn2+/HA ratio for simultaneous and efficient removal of Cd(II), Pb(II), Cu(II), Zn(II), As(III), Sb(III), As(V) and Sb(V) from aqueous environment: Behaviors and mechanisms - Qian Li; Lang Liao; Rui Xu; Zhenguo Wu; Zhe Yin; Yuqi Han; Yan Zhang; Yongbin Yang; Tao Jiang (Journal of Hazardous Materials, 2023)

Self-assembly of Au nanocrystals into large-area 3-D ordered flexible superlattice nanostructures arrays for ultrasensitive trace multi-hazard detection - Wei Liu; Qian Li; Jiabin Wu; Weizhe Wang; Rui Jiang; Chunli Zhou; Shuangbao Wang; Xueming Zhang; Tangyou Sun; Zhimou Xu; Dingsheng Wang (Journal of Hazardous Materials, 2023)

Novel supported low-temperature solid molten salt (SMS) anode materials for Li-ion batteries - Lei Jiang; Ning Han; Tingting Luo; Zhe Zhang; Fenghao Liang; Daoning Wu; Xiaochun Li; Fengjiao Liu; Yichuan Rui; Wei Zhang; Yi Qu; Bohejin Tang (Chemical Engineering Journal, 2023)

Target acquisition of anti-aging manno-oligosaccharide that triggers ECM process via TGF-β/Smads-SIRT1 signalling pathway - Liu Yang; Chengting Zi; Dingkang Chen; Jinyu Li; Rui He; Jiang-Miao Hu (Carbohydrate Polymers, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Paenibacillus alkalitolerans sp. nov., a bacterium isolated from a salt lake of Turpan City in Xinjiang Province, north-west China - Rui Li; Zhou-Tian-Le Zhang; Yun Wang; Gang-Qiang Jiang; Min Yin; Yu Li; Wen-Yong Zhu; Shu-Kun Tang (Folia Microbiologica, 2023)

Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

Flavor components detection and discrimination of isomers in Huaguo tea using headspace-gas chromatography-ion mobility spectrometry and multivariate statistical analysis - Wenhui Lu; Jing Chen; Xuebo Li; Yinghua Qi; Rui Jiang (Analytica Chimica Acta, 2023)

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Interplay of higher plants with lithium pollution: Global trends, meta-analysis, and perspectives - Noman Shakoor; Muhammad Adeel; Imran Azeem; Muhammad Arslan Ahmad; Muhammad Zain; Aown Abbas; Muzammil Hussain; Yaqi Jiang; Pingfan Zhou; Yuanbo Li; Ming Xu; Yukui Rui (Chemosphere, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

Description of a moderately acidotolerant and aerotolerant anaerobic bacterium Acidilutibacter cellobiosedens gen. nov., sp. nov. within the family Acidilutibacteraceae fam. nov., and proposal of Sporanaerobacteraceae fam. nov. and Tepidimicrobiaceae fam. nov. - Hui Fan; Jiang Li; Weidong Wu; Rui Chen; Min Yang; Yinggang Zhang; Lulu Cong; Lirong Dai; Yu Deng; Lei Cheng; Shichun Ma (Systematic and Applied Microbiology, 2023)

Naïve-like conversion of bovine induced pluripotent stem cells from Sertoli cells - Yu Jiang; Ning-Ning Cai; Xing-Lan An; Wen-Qian Zhu; Rui Yang; Bo Tang; Zi-Yi Li; Xue-Ming Zhang (Theriogenology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Electrochemical behavior of gold dissolution with a novel eco-friendly synthetic gold lixiviant - Qian Li; Siyu Dong; Yan Zhang; Rui Xu; Yongbin Yang; Tao Jiang (Minerals Engineering, 2023)

Mechanism of excavation-induced cracking of the protective layer of a rock bench in a large underground powerhouse under high tectonic stress - Yuelin Xia; Xia-Ting Feng; Chengxiang Yang; Shaojun Li; Dingping Xu; Quan Jiang; Rui Kong; Yonghong Li; Zhiguo Li (Engineering Geology, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Homogeneously distributed heterostructured interfaces in rice panicle-like SbBi-Bi2Se3-Sb2Se3 nanowalls for robust sodium storage - Xinyan Li; Shuhao Xiao; Dengji Guo; Jinxia Jiang; Xiaobin Niu; Rui Wu; Taisong Pan; Jun Song Chen (Chemical Engineering Journal, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Assessing psychological factors on farmers' intention to apply organic manure: an application of extended theory of planned behavior - Jing Li; Rui Jiang; Xueyu Tang (Environment, Development and Sustainability, 2022)

Site-directed RNA editing by harnessing ADARs: advances and challenges - Ming Li; Cheng Yan; Yue Jiao; Yuqin Xu; Chen Bai; Rui Miao; Jiying Jiang; Jiao Liu (Functional & Integrative Genomics, 2022)

Effects of two Mn-based nanomaterials on soybean antioxidant system and mineral element homeostasis - Yaqi Jiang; Pingfan Zhou; Tengtao Ma; Muhammad Adeel; Noman Shakoor; Yuanbo Li; Mingshu Li; Manlin Guo; Yukui Rui (Environmental Science and Pollution Research, 2022)

Meshless Surface Wind Speed Field Reconstruction Based on Machine Learning - Nian Liu; Zhongwei Yan; Xuan Tong; Jiang Jiang; Haochen Li; Jiangjiang Xia; Xiao Lou; Rui Ren; Yi Fang (Advances in Atmospheric Sciences, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Human health risk assessment of heavy metals from PM2.5 in China’s 29 provincial capital cities - Li Li; Rui Meng; Yalin Lei; Sanmang Wu; Yong Jiang (Environmental Science and Pollution Research, 2022)

An alanine to valine mutation of glutamyl-tRNA reductase enhances 5-aminolevulinic acid synthesis in rice - Meng Jiang; Shang Dai; Yun-Chao Zheng; Rui-Qing Li; Yuan-Yuan Tan; Gang Pan; Ian Max Møller; Shi-Yong Song; Jian-Zhong Huang; Qing-Yao Shu (Theoretical and Applied Genetics, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Influence of different inoculation densities of black soldier fly larvae (Hermetia illucens) on heavy metal immobilization in swine manure - Dongmei Jiang; Kunhong Jiang; Rui Li; Liangbin Zhao; Zile Liu; Bangjie Xiong; Du Jin; Xiaoxia Hao; Li Zhu; Bo Kang; Lin Bai (Environmental Science and Pollution Research, 2022)

Detection and typing of dengue virus by one-step RT-PCR-based high-resolution melting assay - Rui Tian; Hao Yan; Yang Jiang; Aiping Wu; Ling Li; Zhangnv Yang; Kuangming Yu (Virus Genes, 2022)

Clinical Reference Strategy for the Selection of Treatment Materials for Maxillofacial Bone Transplantation: A Systematic Review and Network Meta-Analysis - Shuxin Zhang; Xinyi Zhang; Yanli Li; Xuran Mao; Rui Liu; Yanxin Qi; Eui-Seok Lee; Heng Bo Jiang (Tissue Engineering and Regenerative Medicine, 2022)

Erratum to: Generating broad-spectrum tolerance to ALS-inhibiting herbicides in rice by base editing - Rui Zhang; Sha Chen; Xiangbing Meng; Zhuangzhuang Chai; Delin Wang; Yuge Yuan; Kunling Chen; Linjian Jiang; Jiayang Li; Caixia Gao (Science China Life Sciences, 2022)

Establishment and optimization of PEG-mediated protoplast transformation in the microalga Haematococcus pluvialis - Chunli Guo; Muhammad Anwar; Rui Mei; Xinyi Li; Di Zhao; Yanan Jiang; Jieyi Zhuang; Chen Liu; Chaogang Wang; Zhangli Hu (Journal of Applied Phycology, 2022)
Genetic manipulation of Haematococcus pluvialis is difficult because of the lack of a stable and convenient transformation system. The pH124-EGFP-Ble vector containing ble as a selective gene and EGFP as a reporter gene was constructed and employed for effective transformation. H. pluvialis protoplasts were obtained by treating with cellulase and macerozeme. Then polyethylene glycol-mediated transformation was established by incubating the protoplast with the vector. To improve the transformation efficiency of H. pluvialis protoplasts, the transformation system was optimized in consideration of different influencing factors, including zeomycin concentration, growth stage, amount of transformed vector, linearization of the vector, and duration of low-intensity illumination. The integration and expression of ble and EGFP was confirmed in the transformants. Moreover, the optimal combination for protoplast transformation of H. pluvialis was determined to be 5 µg of the linearized vector used to transform cells in the log growth phase, and then the transformed protoplasts allowed to recover under low-intensity illumination for 6 h. This study represents and describes the successful development of an H. pluvialis transformation protocol using protoplasts, which will enable convenient genetic manipulation of this important algal species.

Failure mechanisms and risk mitigation of check dams on the Chinese Loess Plateau: A case study at the Gutun Gully - Rui-jun Jiang; Mao-sheng Zhang; Li Feng; Ping-ping Sun (Journal of Mountain Science, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Hippocampal Activated Microglia May Contribute to Blood–Brain Barrier Impairment and Cognitive Dysfunction in Post-Traumatic Stress Disorder-Like Rats - Kun Ni; Jixiang Zhu; Xuan Xu; Yue Liu; Shuai Yang; Yulin Huang; Rui Xu; Li Jiang; Juan Zhang; Wei Zhang; Zhengliang Ma (Journal of Molecular Neuroscience, 2022)

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Physiological Responses of Ribosomal Protein S12 K43 Mutants of Corynebacterium glutamicum - Guihong Zhao; Rui Su; Meng Yuan; Hongkun Ma; Taidong Bo; Hao Jiang; Chen Wu; Yanjun Li (Current Microbiology, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Surface wind and vertical extent features of the explosive cyclones in the Northern Hemisphere based on the ERA‐I reanalysis data - Li‐Zhi Jiang; Shen‐Ming Fu; Jian‐Hua Sun; Rui Fu; Wan‐Li Li; Si‐Xiong Zhao; Hui Wang (International Journal of Climatology, 2022)
Although explosive cyclones (ECs) have long been a focus of research, there remains a lack of knowledge of the statistical characteristics of their associated maximum surface winds and vertical extents. This study fills this gap by conducting a targeted statistical analysis of ECs in the Northern Hemisphere using the ERA‐I reanalysis data during a 40‐year period. Some new findings are obtained: (a) The average location of formation of ECs undergoes a notable westward and equatorward shift from September to April in the next year which is consistent with the location variations of sea surface temperature's strong gradients in subtropical regions. (b) Extreme ECs with a deepening rate more than 2.0 Bergeron or with a longer lifespan more than 10 days tend to have a larger occurrence number over the Northern Atlantic Ocean than over the Northern Pacific. (c) The maximum surface wind associated with an EC tends to appear between the EC reaching its maximum deepening rate and reaching its minimum central pressure. (d) The northeastern quadrant of ECs accounts for the highest proportion of maximum surface wind and strongest wind speed, as the baroclinic energy conversion is generally strongest in this quadrant. (e) Over 60% of ECs belong to a type of vertically deep cyclone (ECs' top levels show close relationship to ascending motions within their central regions), and they tend to reach their maximum vertical extent around the time when they reach their minimum central pressures. (f) The highest top levels of ECs exhibit an overall upward extending trend as their minimum central pressure decreases or their maximum deepening rate increases.

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

A feasible vibration measurement and active control method of reinforced concrete lightweight pier railway bridges for heavy-haul monorail trains - Ling-kun Chen; Li-zhong Jiang; Rui Li; Qiao Li; Ming Zhang; Nan Zhang; Jin-zhang Luo; Liang Ling; Sheng-yang Zhu (European Journal of Environmental and Civil Engineering, 2022)

Kangiella shandongensis sp. nov., a novel species isolated from saltern in Yantai, China - Li-Yang Peng; Rui Yin; Shu-Kun Gao; Hui-Ning Jiang; Xiao-Xiao Liu; Yu Ma; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2022)

Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

Synthesis, characterization and antitumor mechanism investigation of ruthenium(II) polypyridyl complexes with artesunate moiety - Bi-Chun Chen; Jun-Jian Lu; Ning Jiang; Xiu-Rong Ma; Rong-Tao Li; Rui-Rong Ye (JBIC Journal of Biological Inorganic Chemistry, 2021)

cDNA cloning and expression analysis of glutaredoxin 3 in black tiger shrimp Penaeus monodon - Rui Fan; Yundong Li; Shigui Jiang; Song Jiang; Qibin Yang; Lishi Yang; Jianhua Huang; Falin Zhou (Aquaculture International, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Qaidamihabitans albus gen. nov., sp. nov., a new member of the family Pseudonocardiaceae, and transfer of Prauserella shujinwangii to Qaidamihabitans gen. nov. as Qaidamihabitans shujinwangii comb. nov. - Li-Sha Tian; Gang-Qiang Jiang; Rui Li; Ping Ni; Chuan-En Li; Hong-Yan Zhang; Juan Wang; Xiao-Ping Zhang; Yun Wang; Shu-Kun Tang (Archives of Microbiology, 2021)

Generating broad-spectrum tolerance to ALS-inhibiting herbicides in rice by base editing - Rui Zhang; Sha Chen; Xiangbing Meng; Zhuangzhuang Chai; Delin Wang; Yuge Yuan; Kunling Chen; Linjian Jiang; Jiayang Li; Caixia Gao (Science China Life Sciences, 2021)

Glycomyces salinus sp. nov., an actinomycete isolated from a hypersaline habitat - Rui Li; Gang-Qiang Jiang; Yun Wang; Yi-Guang Chen; En-Min Zhou; Shu-Kun Tang (Archives of Microbiology, 2021)

Numerical modeling of 3D DC resistivity method in the mixed space-wavenumber domain - Shi-Kun Dai; Jia-Xuan Ling; Qing-Rui Chen; Kun Li; Qian-Jiang Zhang; Dong-Dong Zhao; Ying Zhang (Applied Geophysics, 2021)

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

Screening and Analysis of Multiclass Veterinary Drug Residues in Animal Source Foods using UPLC-Q-Exactive Orbitrap/MS - Wentao Zhao; Rui Jiang; Wenping Guo; Chao Guo; Shilei Li; Juanqiang Wang; Shouwei Wang; Yingying Li (Bulletin of Environmental Contamination and Toxicology, 2021)
A rapid, simple, and sensitive method of detecting veterinary drug residues in animal food sources, including poultry and pork, was developed and validated. The method was optimized for over 155 veterinary drugs of 21 different classes. Sample pretreatment included a simple solid-liquid extraction step with 0.2% formic acid-acetonitrile-water and a purification step with a PRiME HLB (hydrophile-lipophile balance) solid-phase extraction cartridge. Data were collected using ultra-high-performance liquid chromatography coupled to Quadrupole-Exactive Orbitrap mass spectrometry. The limits of detection of 155 veterinary drugs ranged from 0.1 µg/kg to 10 µg/kg. The recovery rates were between 79.2 and 118.5 % in all matrices studied, with relative standard deviation values less than 15% (n = 6). The evaluated method allows the reliable screening, quantification, and identification of 155 veterinary drug residues in animal source food and has been successfully applied in authentic samples.

Heterogeneity of tight sandstone reservoirs based on fractal theory: the Xu-6 member of Xujiahe Formation in Guang'an area, central Sichuan Basin - Fang Shen; Liang Yue; Ziliang Liu; Wei Yang; Kaarel Mänd; Hui Jin; Fengjie Li; Yue Zhou; Minghe Zhang; Rui Jiang (Arabian Journal of Geosciences, 2021)

Longitudinal associations of sleep duration and sleep quality with coronary heart disease risk among adult population: classical meta-analysis and Bayesian network meta-analysis - Rui Zeng; Yu-ting Jiang; Tian-wu Chen; Dan-dan Guo; Rui Li (Sleep and Biological Rhythms, 2021)

A new dineolignan with anti- β -amyloid aggregation activity from the fruits of crataegus pinnatifida bge - Peng Zhao; Li-Li Lou; Hao Zhang; Rui Guo; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Antifungal Effect of Long Noncoding RNA 9708-1 in the Vulvovaginal Candidiasis Murine Model - Ying Wu; Lisha Jiang; Lingling Zhang; Xia Liu; Lina Yan; Ting Luan; Can Rui; Zhiyuan Mao; Chong Fan; Yu Liu; Ping Li; Xin Zeng (Mycopathologia, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida spp. affects 70–75% of women at least once during their lives. We aim to elucidate the potential mechanism of VVC and investigate the therapeutic effects of long noncoding RNA 9708-1. Female BALB/c mice were randomized to four treatment groups, including the blank control group, VVC control group, vehicle control group and lncRNA 9708-1-overexpressed group. Mice were euthanized on Day 4, Day 7 and Day 14 after treatment. Colony-forming unit (CFU) was measured, and the inflammation was detected by hematoxylin and eosin (H&E). Gene and protein expression levels of lncRNA 9708-1 and FAK were determined by real-time PCR, Western blot and immunohistochemistry. The overexpression of lncRNA 9708-1 significantly decreased the fungal load from Day 4 to 7. H&E staining indicated that the impaired histological profiles were improved in lncRNA 9708-1-overexpressed group. LncRNA 9708-1 led to a significant increase in FAK level of vagina tissue which is expressed mainly in epithelial basal layer. This study suggests that lncRNA 9708-1 played a protective role on murine experimental VVC by upregulating the expression levels of FAK.

Experimental validation of a new semi-empirical impact force model of the dry granular flow impact against a rigid barrier - Yuan-Jun Jiang; Xiao-Yi Fan; Li-Jun Su; Si-you Xiao; Jing Sui; Rui-Xiao Zhang; Yue Song; Zhi-Wen Shen (Landslides, 2021)

Isolation, characterization, and application of Salmonella paratyphi phage KM16 against Salmonella paratyphi biofilm - Liming Jiang; Rui Zheng; Qiangming Sun; Chenghua Li (Biofouling, 2021)

Abiotic and biotic controls of soil dissolved organic nitrogen along a precipitation gradient on the Tibetan plateau - Lili Jiang; Shiping Wang; Zhe Pang; Changshun Wang; Fandong Meng; Zhichun Lan; Xiaoqi Zhou; Yaoming Li; Zhenhua Zhang; Caiyun Luo; Davey L. Jones; Yichao Rui; et al. (Plant and Soil, 2021)

GmNAC06, a NAC domain transcription factor enhances salt stress tolerance in soybean - Ming Li; Rui Chen; Qiyan Jiang; Xianjun Sun; Hui Zhang; Zheng Hu (Plant Molecular Biology, 2021)
Key message We found GmNAC06 plays an important role in salt stress responses through the phenotypic, physiological and molecular analyses of OE, VC, and Mutant composite soybean. Abstract Salinization affects 20% of all cultivated land worldwide because of the high salinity of irrigation water and the excessive use of water, and this amount is increasing daily. NAC (NAM, ATAF, and CUC) have been found to be involved in salt stress. In this study, a soybean NAC gene, GmNAC06 (Glyma06g21020.1), was cloned and functionally characterized. The results of expression analysis suggested that salt stress could influence the expression level of GmNAC06 . The subcellular localization analysis results suggested that GmNAC06 may function as a transcription factor. Under salt stress, the overexpression technology combined with CRISPR-Cas9 system found that GmNAC06 could cause the accumulation of proline and glycine betaine to alleviate or avoid the negative effects of ROS; similarly, it could control the Na + /K + ratios in hairy roots to maintain ionic homeostasis. The fresh weight of the transgenic hairy roots and the histochemical ROS staining of wild leaves suggested that transgenic hairy roots influence the function of wild leaves under salt stress conditions. Moreover, the expression levels of GmUBC2 and GmHKT1 were higher in the GmNAC06 hairy roots than in the control. Thus, the overexpression of GmNAC06 in hairy roots notably causes an entire composite plant to exhibit salt tolerance. The phenotype of composite soybean plants and transgenic Arabidopsis plants suggest that GmNAC06 plays a role in response to salt stress and could be useful in generating salt tolerant transgenic crops.

Combining forecast of landslide displacement based on chaos theory - Xunchang Li; Chao Jiang; Rui Xu; Wei Yang; HaoHao Wang; Yu Zou (Arabian Journal of Geosciences, 2021)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Role of Chromatin Remodeling Genes and TETs in the Development of Human Midbrain Dopaminergic Neurons - Li Xiang; Guobin Huang; Wenjing Shu; Chunli Gong; Nan Cao; Rui Chen; Jixi Li; Hao Lu; Gaofeng Jiang (Stem Cell Reviews and Reports, 2020)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Effects of crop straw biochars on aluminum species in soil solution as related with the growth and yield of canola (Brassica napus L.) in an acidic Ultisol under field condition - Wen-rui Zhao; Jiu-yu Li; Kai-ying Deng; Ren-yong Shi; Jun Jiang; Zhi-neng Hong; Wei Qian; Xian He; Ren-kou Xu (Environmental Science and Pollution Research, 2020)

Ambient temperature alters body size and gut microbiota of Xenopus tropicalis - Jiaying Li; Junpeng Rui; Yulong Li; Na Tang; Songping Zhan; Jianping Jiang; Xiangzhen Li (Science China Life Sciences, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

First report of broad bean wilt virus 2 infection in eggplant in China - Peng-Huan Rui; Lei Jiang; Shuai Li; Xi-Zi Jiang; Qing-Qing Zhao; Ji Ying Feng; Tong Jiang (Journal of Plant Pathology, 2020)

Plasma Endostatin Levels at Acute Phase of Ischemic Stroke Are Associated with Post-Stroke Cognitive Impairment - Sifan Qian; Ruyi Li; Chenhuan Zhang; Rui Zhang; Daoxia Guo; Xiaoqing Bu; Aili Wang; Hao Peng; Jing Chen; Yonghong Zhang; Jiang He; Tan Xu; et al. (Neurotoxicity Research, 2020)

Bionic design in anti-bending and lightweight tube based on the tarsometatarsus of ostrich - Rui Zhang; Hao Pang; Dianlei Han; Shuliang Xue; Lei Jiang; Dong Li; Lige Wen; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)

Community structure of Anaeromyxobacter in Fe(III) reducing enriched cultures of paddy soils - Kun Wang; Rong Jia; Lina Li; Rui Jiang; Dong Qu (Journal of Soils and Sediments, 2020)

A novel neural computational model of generalized periodic discharges in acute hepatic encephalopathy - Jiang-Ling Song; Luis Paixao; Qiang Li; Si-Hui Li; Rui Zhang; M. Brandon Westover (Journal of Computational Neuroscience, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Model test on failure and control mechanism of surrounding rocks in tunnels with super large sections - Rui Pan; Qi Wang; Bei Jiang; Shucai Li (Arabian Journal of Geosciences, 2019)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

A new coumarin from Juglans mandshurica Maxim induce apoptosis in hepatocarcinoma cells - Li-Li Lou; Peng Zhao; Zhuo-Yang Cheng; Rui Guo; Guo-Dong Yao; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Mechanical Effect Analysis and Comparative Site Tests on Surrounding Rock with Different Bolt Anchoring Lengths and Pre-tightening Forces - Qi Wang; Hongtao Wang; Rui Pan; Shucai Li; Manchao He; Bei Jiang; Qian Qin; Chong Zhang; Yingdong Xu (Geotechnical and Geological Engineering, 2019)

Brick tea consumption is a risk factor for dental caries and dental fluorosis among 12-year-old Tibetan children in Ganzi - Rui Zhang; Li Cheng; Tao Zhang; Ting Xu; Meng Li; Wei Yin; Qingling Jiang; Yingming Yang; Tao Hu (Environmental Geochemistry and Health, 2019)

Depositional and diagenetic controls on the reservoir quality of Upper Triassic Chang-7 tight oil sandstones, southwestern Ordos basin, China - Ai Wang; Dakang Zhong; Haihua Zhu; Lele Guo; Zhuopei Li; Yangjinfeng Jiang; Xueqi Yang; Rui Xie; Xiaowei Zheng (Geosciences Journal, 2019)

Temperature-control-induced masculinization in tiger puffer Takifugu rubripes - He Zhou; Zixin Zhuang; Rui Zhang; Qizheng Xu; Yuting Liang; Zhiqiang Jiang; Xia Li; Tianyu Ma; Yajuan Li (Journal of Oceanology and Limnology, 2019)

Study on Surrounding Rock Stability of Small Clear-Distance Twin Highway Tunnel with Eight Lanes - Qing Jiang; Shu-guang Song; Tao Li; Kang Wang; Rui-hai Gu (Geotechnical and Geological Engineering, 2019)

Alkaloids from Juglans Mandshurica maxim induce distinctive cell death in hepatocellular carcinoma cells - Li-Li Lou; Zhuo-Yang Cheng; Rui Guo; Guo-Dong Yao; Shao-Jiang Song (Natural Product Research, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

Brain Network Reconfiguration During Motor Imagery Revealed by a Large-Scale Network Analysis of Scalp EEG - Fali Li; Chanlin Yi; Limeng Song; Yuanling Jiang; Wenjing Peng; Yajing Si; Tao Zhang; Rui Zhang; Dezhong Yao; Yangsong Zhang; Peng Xu (Brain Topography, 2019)

Transcriptome sequencing to reveal the genetic regulation of leaf margin variation at early stage in birch - Xiuyan Bian; Chang Qu; Manman Zhang; Yidi Li; Rui Han; Jing Jiang; Guifeng Liu (Tree Genetics & Genomes, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Plant organic N uptake maintains species dominance under long-term warming - Lili Jiang; Shiping Wang; Pang Zhe; Xingliang Xu; Paul Kardol; Yaoming Li; Lirong Zhang; Yanfen Wang; Zhong Lei; Zhichun Lan; Paul W. Hill; Zhenhua Zhang; et al. (Plant and Soil, 2018)

Complete nucleotide sequence of a novel monopartite begomovirus infecting Ageratum conyzoides in China - Pengbai Li; Chenchen Jing; Rui Wang; Jiang Du; Gentu Wu; Mingjun Li; Xianchao Sun; Ling Qing (Archives of Virology, 2018)

Augmenter of liver regeneration promotes mitochondrial biogenesis in renal ischemia–reperfusion injury - Li-li Huang; Rui-ting Long; Gui-ping Jiang; Xiao Jiang; Hang Sun; Hui Guo; Xiao-hui Liao (Apoptosis, 2018)

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

The role of autophagy in pulmonary hypertension: a double-edge sword - Rui Chen; Meiping Jiang; Bo Li; Wei Zhong; Zhongqun Wang; Wei Yuan; Jinchuan Yan (Apoptosis, 2018)

Anemia and Iron Status Among Different Body Size Phenotypes in Chinese Adult Population: a Nation-Wide, Health and Nutrition Survey - Jiang Li; Cheng Xiao; Hui Yang; Yun Zhou; Rui Wang; Yongtong Cao (Biological Trace Element Research, 2018)

Three-dimensional numerical modeling of gravity anomalies based on Poisson equation in space-wavenumber mixed domain - Shi-Kun Dai; Dong-Dong Zhao; Qian-Jiang Zhang; Kun Li; Qing-Rui Chen; Xu-Long Wang (Applied Geophysics, 2018)

Fast 3D forward modeling of the magnetic field and gradient tensor on an undulated surface - Kun Li; Long-Wei Chen; Qing-Rui Chen; Shi-Kun Dai; Qian-Jiang Zhang; Dong-Dong Zhao; Jia-Xuan Ling (Applied Geophysics, 2018)

The distribution and partitioning of trace metals (Pb, Cd, Cu, and Zn) and metalloid (As) in the Beijiang River - Rui Li; Changyuan Tang; Yingjie Cao; Tao Jiang; Jianyao Chen (Environmental Monitoring and Assessment, 2018)

Comparative growth increments of gladius surface and cross-sections to estimate Sthenoteuthis oualaniensis age - Xue Feng Wang; Bi Lin Liu; Jian Hua Li; Rui Jiang; Jing Yuan Lin; Teng Li (Marine Biology, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

U–Pb zircon, geochemical and Sr–Nd–Hf isotopic constraints on age and origin of the intrusions from Wunugetushan porphyry deposit, Northeast China: implication for Triassic–Jurassic Cu–Mo mineralization in Mongolia–Erguna metallogenic belt - Kui-Feng Mi; Zhen-Jiang Liu; Rui-Bin Liu; Chun-Feng Li; Jian-Ping Wang; Run-Min Peng (International Geology Review, 2018)

Phenylpropanoids from the fruits of Nicandra physaloides and their anti-inflammatory activities - Bing You Yang; Yan Liu; Hai Bing Jiang; Zhen Peng Xu; Rui Guo; Rui Wang; Xiao Mao Li; Hai Xue Kuang (Natural Product Research, 2017)

Detection and phylogenetic analysis of Mycoplasma hyopneumoniae from Tibetan pigs in western China - Gang Qiu; Yapei Rui; Kun Li; Shucheng Huang; Zhaoqing Han; Xiaoqiang Wang; Wenteng Jiang; Houqiang Luo; Yanfang Lan; Jiakui Li (Tropical Animal Health and Production, 2017)

Limit Analysis of Roof Falling in Roadway with Water-Rich Surrounding Rock - Bei Jiang; Qi Wang; Li Gao; Shucai Li; Chong Zhang; Hongke Gao; Rui Pan (Geotechnical and Geological Engineering, 2017)

Research on differences of spillover effects between international crude oil price and stock markets in China and America - Zhenhua Liu; Zhihua Ding; Rui Li; Xin Jiang; JyS. Wu; Tao Lv (Natural Hazards, 2017)

Inheritance, fine-mapping, and candidate gene analyses of resistance to soybean mosaic virus strain SC5 in soybean - Adhimoolam Karthikeyan; Kai Li; Hua Jiang; Rui Ren; Cui Li; Haijian Zhi; Shouyi Chen; Junyi Gai (Molecular Genetics and Genomics, 2017)

Comparison of dust emissions, transport, and deposition between the Taklimakan Desert and Gobi Desert from 2007 to 2011 - SiYu Chen; JianPing Huang; JingXin Li; Rui Jia; NanXuan Jiang; LiTai Kang; XiaoJun Ma; TingTing Xie (Science China Earth Sciences, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Performance analysis of a Kalman filter carrier phase tracking loop - Rui Jiang; Kedong Wang; Shihan Liu; Yong Li (GPS Solutions, 2017)

Microvesicles shed from microglia activated by the P2X7-p38 pathway are involved in neuropathic pain induced by spinal nerve ligation in rats - Jian Li; Xiangnan Li; Xin Jiang; Mei Yang; Rui Yang; Geoffrey Burnstock; Zhenghua Xiang; Hongbin Yuan (Purinergic Signalling, 2017)

Dietary Zinc Oxide Modulates Antioxidant Capacity, Small Intestine Development, and Jejunal Gene Expression in Weaned Piglets - Cui Zhu; Hang Lv; Zhuang Chen; Li Wang; Xiuju Wu; Zhongjian Chen; Weina Zhang; Rui Liang; Zongyong Jiang (Biological Trace Element Research, 2017)

Biological traits yield divergent phylogeographical patterns between two aphids living on the same host plants - Fang Fang; Jing Chen; Li‐Yun Jiang; Rui Chen; Ge‐Xia Qiao (Journal of Biogeography, 2017)
Aim Animals' phylogeographical patterns are frequently explained by Pleistocene glacial fluctuations and topographical environments. However, species‐specific biological traits are thought to have profound impacts on distribution patterns, particularly in aphids. We hypothesize that the phylogeographical patterns and/or population dynamics of two sympatric aphids may be different due to their different reproductive modes and feeding sites, even though they share the same hosts and environmental conditions. Location China. Methods We explored our hypothesis in Chaitophorus saliniger and Tuberolachnus salignus , two aphids that share the same host plants (genus Salix ) but differ biologically. Chaitophorus saliniger is characterized by alternating sexual and asexual reproduction and only feeds on willow leaves, whereas T. salignus has obligate asexual reproduction and feeds on trunks and branches. The genetic diversity, population structure and demographic history of the aphids were analysed based on both mitochondrial DNA (cytochrome c oxidase subunit I and cytochrome b ) and nuclear DNA (translation elongation factor 1 alpha). Ecological niche models ( ENM s) were used to explore historical changes in distribution. The chief environmental variables that discriminate the different haplogroups were identified through multivariate statistical analysis. Results There were striking differences in the phylogeographical patterns between the species. The sexual C. saliniger exhibited higher genetic diversity and population variations than the asexual T. salignus . According to genetic analyses and ENM s, both species experienced glacial contraction and post‐glacial expansion. Multivariate statistical analysis revealed that the climatic differences between the divergent haplogroups were explained by principal components mainly loaded with temperature and elevation. Main conclusions Our results suggest that species‐specific biological traits and historical climate fluctuations have both shaped the current phylogeographical patterns of both aphid species. Their distinct genetic diversity and population structures highlight the importance of intrinsic biological features in driving phylogeographical patterns.

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Quantitative determination constraints on dolomitization model for the Upper Permian Changxing reservoir dolomites of Northeastern Sichuan Basin, Southwestern China - Rui Zhao; Ya Sheng Wu; Hong Xia Jiang; Qing Song Liu; Li Jing Liu (Carbonates and Evaporites, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Dust aerosol properties and radiative forcing observed in spring during 2001–2014 over urban Beijing, China - Xingna Yu; Rui Lü; K. Raghavendra Kumar; Jia Ma; Qiuju Zhang; Yilun Jiang; Na Kang; Suying Yang; Jing Wang; Mei Li (Environmental Science and Pollution Research, 2016)

Activation of Autophagy Contributes to the Angiotensin II-Triggered Apoptosis in a Dopaminergic Neuronal Cell Line - Qing Gao; Teng Jiang; Hong-Rui Zhao; Liang Wu; You-Yong Tian; Zhou Ou; Li Zhang; Yang Pan; Jie Lu; Ying-Dong Zhang (Molecular Neurobiology, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Reconstruction of historical lead contamination and sources in Lake Hailing, Eastern China: a Pb isotope study - Rui Zhang; Minglei Guan; Yujie Shu; Liya Shen; Xixi Chen; Fan Zhang; Tiegang Li; Tingchen Jiang (Environmental Science and Pollution Research, 2016)

A Sensitive and Selective Fluorescent Coumarin-Based Probe for Detection of Hypochlorite ion and its Application to Cellular Imaging - Hui-Li Gong; Yi Jiang; Rui-Chun Hou; Xiang-Qian Ding (Journal of Fluorescence, 2016)

Ochrobactrum endophyticum sp. nov., isolated from roots of Glycyrrhiza uralensis - Li Li; Yan-Qiong Li; Zhao Jiang; Rui Gao; Salam Nimaichand; Yan-Qing Duan; Dilfuza Egamberdieva; Wei Chen; Wen-Jun Li (Archives of Microbiology, 2016)

Evolutionary history of Apocheima cinerarius (Lepidoptera: Geometridae), a female flightless moth in northern China - Shuxian Liu; Nan Jiang; Dayong Xue; Rui Cheng; Yanhua Qu; Xinxin Li; Fumin Lei; Hongxiang Han (Zoologica Scripta, 2016)
The alterations in the phylogeographical structures of insects in response to the uplift of the Qinghai–Tibet Plateau and the Quaternary glaciations in eastern Asia, particularly in northern China, remain largely unknown. In this study, we selected Apocheima cinerarius , a moth with flightless females, using molecular data (complete mitochondrial genomes and nuclear data) and ecological niche modelling ( ENM ) to investigate the effects of paleoclimatic changes on the evolutionary history of insects in the area of northern China. The phylogenetic tree of complete mitochondrial genomes indicated that there were two lineages, the western and eastern lineages. The nuclear gene analyses also detected unique haplotypes in each lineage. Time of the most recent common ancestor ( TMRCA ) of the two lineages was approximately in Early–Middle Pleistocene. Bayesian skyline plots revealed that the western lineage underwent a population expansion event after the Last Glacial Maximum, whereas the eastern lineage underwent expansion between the Last Interglacial and the Last Glacial Maximum. Our results suggest that A. cinerarius expanded eastward from western sites until the moth was distributed across the entire region of northern China. Then, A . cinerarius underwent contraction into isolated glacial refugia followed by subsequent expansion driven by Pleistocene climate changes, which established a narrow sympatric area. Our results indicate that the Quaternary environmental fluctuations had profound influences on the diversification and demography of an insect in northern China, and the same species in north‐western China and north‐eastern China have different demographic histories.

Kupffer-cell-expressed transmembrane TNF-α is a major contributor to lipopolysaccharide and D-galactosamine-induced liver injury - Peng Yang; Wenjing Zhou; Chenxi Li; Meng Zhang; Yaping Jiang; Rui Jiang; Hongping Ba; Cheng Li; Jing Wang; Bingjiao Yin; Feili Gong; Zhuoya Li (Cell and Tissue Research, 2016)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

Ectopic expression of UGT75D1, a glycosyltransferase preferring indole-3-butyric acid, modulates cotyledon development and stress tolerance in seed germination of Arabidopsis thaliana - Gui-Zhi Zhang; Shang-Hui Jin; Xiao-Yi Jiang; Rui-Rui Dong; Pan Li; Yan-Jie Li; Bing-Kai Hou (Plant Molecular Biology, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

A new highly oxygenated daphnane diterpene esters from the flower buds of Daphne genkwa - Hai-Long Jiang; Rui Wang; Jian-Yong Li; Yan-Ping Shi (Natural Product Research, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Increased Expression of Protease-Activated Receptor 2 and 4 Within Dorsal Root Ganglia in a Rat Model of Bone Cancer Pain - Yanju Bao; Wei Hou; Liping Yang; Rui Liu; Yebo Gao; Xiangying Kong; Zhan Shi; Weidong Li; Honggang Zheng; Shulong Jiang; Baojin Hua (Journal of Molecular Neuroscience, 2015)

A novel missense mutation in collagenous domain of EDA gene in a Chinese family with X-linked hypohidrotic ectodermal dysplasia - DAXU LI; RAN XU; FUMENG HUANG; BIYUAN WANG; YU TAO; ZIJIAN JIANG; HAIRUI LI; JIANFENG YAO; PENG XU; XIAOKANG WU; LE REN; RUI ZHANG; et al. (Journal of Genetics, 2015)

Next-generation sequencing-based molecular diagnosis of 82 retinitis pigmentosa probands from Northern Ireland - Li Zhao; Feng Wang; Hui Wang; Yumei Li; Sharon Alexander; Keqing Wang; Colin E. Willoughby; Jacques E. Zaneveld; Lichun Jiang; Zachry T. Soens; Philip Earle; David Simpson; et al. (Human Genetics, 2015)

Chemical modification, characterization and bioactivity of a released exopolysaccharide (r-EPS1) from Lactobacillus plantarum 70810 - Kun Wang; Wei Li; Xin Rui; Teng Li; Xiaohong Chen; Mei Jiang; Mingsheng Dong (Glycoconjugate Journal, 2015)

Composition and variation analysis of TCR β-chain CDR3 repertoire in the thymus and spleen of MRL/lpr mouse at different ages - Zhou Li; Ma Long; Liu ChunMei; Shi Bin; Yu Jiang; Ma Rui; Ma Qingqing; Yao XinSheng (Immunogenetics, 2015)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

A new algorithm for fine acquisition of GPS carrier frequency - Kedong Wang; Rui Jiang; Yong Li; Ning Zhang (GPS Solutions, 2014)

Anti-depressive activities and biotransformation of timosaponin B-III and its derivatives - WeiXin Jiang; Jing Guo; Rui Xue; KaiCheng Zhu; ZhiXiong Li; MingCang Chen; ChengGang Huang (Natural Product Research, 2014)

DNA Methylation: Roles in Rheumatoid Arthritis - Feng-Lai Yuan; Xia Li; Rui-Sheng Xu; Dong-Lin Jiang; Xiao-Gang Zhou (Cell Biochemistry and Biophysics, 2014)

Protective Effects of Selenium on Mercury Induced Immunotoxic Effects in Mice by Way of Concurrent Drinking Water Exposure - Xuan Li; Daqiang Yin; Jiang Li; Rui Wang (Archives of Environmental Contamination and Toxicology, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

Hemoglobin-Induced Nitric Oxide Synthase Overexpression and Nitric Oxide Production Contribute to Blood–Brain Barrier Disruption in the Rat - Shuo Yang; Yizhao Chen; Xinqing Deng; Weiping Jiang; Bing Li; Zhenghao Fu; Mouxuan Du; Rui Ding (Journal of Molecular Neuroscience, 2013)

Characterizing the microbial culprit of white spot disease of the conchocelis stage of Porphyra yezoensis (Bangiales, Rhodophyta) - Xiangyu Guan; Jinbo Li; Zhe Zhang; Fuchao Li; Rui Yang; Peng Jiang; Song Qin (Journal of Applied Phycology, 2013)

Cellular boron allocation and pectin composition in two citrus rootstock seedlings differing in boron-deficiency response - Gui-Dong Liu; Rui-Dong Wang; Lei-Chao Liu; Li-Shu Wu; Cun-Cang Jiang (Plant and Soil, 2013)

Genome-wide Analysis of the Distribution of AP2/ERF Transcription Factors Reveals Duplication and Elucidates their Potential Function in Chinese Cabbage (Brassica rapa ssp. pekinensis) - Meng-Yao Li; Feng Wang; Qian Jiang; Rui Li; Jing Ma; Ai-Sheng Xiong (Plant Molecular Biology Reporter, 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

A novel Trichoderma species isolated from soil in Guizhou, T. guizhouense - Qi-Rui Li; Ping Tan; Yu-Lan Jiang; Kevin D. Hyde; Eric H. C. Mckenzie; Ali H. Bahkali; Ji-Chuan Kang; Yong Wang (Mycological Progress, 2013)

Genomewide analysis of the chitinase gene family in Populus trichocarpa - CONG JIANG; RUI FANG HUANG; JIA LIANG SONG; MIN REN HUANG; LI AN XU (Journal of Genetics, 2013)

Effect of Long-Term Vinasse Application on Physico-chemical Properties of Sugarcane Field Soils - Ze-Pu Jiang; Yang-Rui Li; Guang-Po Wei; Qing Liao; Tian-Ming Su; Yan-Cheng Meng; Hai-Ying Zhang; Chang-Yan Lu (Sugar Tech, 2012)

Boron distribution and mobility in navel orange grafted on citrange and trifoliate orange - Gui-Dong Liu; Rui-Dong Wang; Li-Shu Wu; Shu-Ang Peng; Yun-Hua Wang; Cun-Cang Jiang (Plant and Soil, 2012)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Macronutrients Absorption and Surface Runoff Losses Under Different Fertilizer Treatments in Sugarcane Field - Tian-Ming Su; Yang-Rui Li; Guang-Po Wei; Ze-Pu Jiang; Qing Liao; Shu-Biao Zhu (Sugar Tech, 2012)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Mantle-derived noble gases in ore-forming fluids of the granite-related Yaogangxian tungsten deposit, Southeastern China - Rui-Zhong Hu; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Jian-Tang Peng; You-Qiang Qi; Li-Yan Wu; Wen-Feng Wei (Mineralium Deposita, 2012)

Effects of flue gas desulfurization gypsum by-products on microbial biomass and community structure in alkaline–saline soils - Ming Li; Lili Jiang; Zhaojun Sun; Jinzhi Wang; Yichao Rui; Lei Zhong; Yanfen Wang; Paul Kardol (Journal of Soils and Sediments, 2012)

Genetic characterization of Aleutian mink disease viruses isolated in China - Yanwu Li; Juan Huang; Yun Jia; Yijun Du; Ping Jiang; Rui Zhang (Virus Genes, 2012)

Gene expression profile of campylobacter jejuni-induced GBS in bama miniature pigs - Feng Xue; Dexin Zeng; Fei Xu; Rui Zhang; Yang Chen; Yuefei Yang; Xiaobo Wang; Zhenzhong Li; Xiaorong Zhang; Yuan Jiang (Cell and Tissue Research, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

Comparative proteomic and radiobiological analyses in human lung adenocarcinoma cells - Rui Wei; Yingjin Zhang; Liangfang Shen; Wuzhong Jiang; Cui Li; Meizuo Zhong; Yun Xie; Dingyi Yang; Lili He; Qing Zhou (Molecular and Cellular Biochemistry, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

He and Ar isotopic compositions and genetic implications for the giant Shizhuyuan W–Sn–Bi–Mo deposit, Hunan Province, South China - Li-Yan Wu; Rui-Zhong Hu; Jian-Tang Peng; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Qiao-Yun Wang; Ya-Ying Liu (International Geology Review, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Chemical constituents of Gentiana macrophylla Pall. - Zhi-Bo Jiang; Hong-Li Liu; Xiao-Qing Liu; Ji-Ning Shang; Jia-Rui Zhao; Cheng-Shan Yuan (Natural Product Research, 2010)

Identification, localization, and characterization of putative USP genes in barley - Wei-Tao Li; Yu-Ming Wei; Ji-Rui Wang; Chun-Ji Liu; Xiu-Jin Lan; Qian-Tao Jiang; Zhi-En Pu; You-Liang Zheng (Theoretical and Applied Genetics, 2010)

Molecular characterization of a member of a new species of grapevine viroid - Dongmei Jiang; Rui Guo; Zujian Wu; Hongqing Wang; Shifang Li (Archives of Virology, 2009)

13C abundance, water-soluble and microbial biomass carbon as potential indicators of soil organic carbon dynamics in subtropical forests at different successional stages and subject to different nitrogen loads - Hua-Jun Fang; Gui-Rui Yu; Shu-Lan Cheng; Jiang-Ming Mo; Jun-Hua Yan; Shenggong Li (Plant and Soil, 2009)

Molecular characterization of grapevine yellow speckle viroid-2 (GYSVd-2) - Dongmei Jiang; Zhixiang Zhang; Zujian Wu; Rui Guo; Hongqing Wang; Peige Fan; Shifang Li (Virus Genes, 2009)

A suicidal DNA vaccine co-expressing two major membrane-associated proteins of porcine reproductive and respiratory syndrome virus antigens induce protective responses - Yunbo Jiang; Liurong Fang; Shaobo Xiao; Bin Li; Yongfei Pan; Rui Luo; Huanchun Chen (Biotechnology Letters, 2009)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

Heterologous expression and characterization of a proxidomal ascorbate peroxidase from Populus tomentosa - Hai Lu; Rui-Li Han; Xiang-Ning Jiang (Molecular Biology Reports, 2009)

Effects of RNA interference-induced tryptase down-regulation in P815 cells on IL-6 and TNF-α release of endothelial cells - Yi-feng Jiang; Feng-di Zhao; Xiao-bo Li; Yan-xia Ning; Xiu-ling Zhi; Rui-zhe Qian; Lian-hua Yin (Journal of Zhejiang University-SCIENCE B, 2008)

Cadmium Accumulation in the Edible Parts of Different Cultivars of Radish, Raphanus sativus L., and Carrot, Daucus carota var. sativa, Grown in a Cd-contaminated Soil - Rui-Lun Zheng; Hua-Fen Li; Rong-Feng Jiang; Fu-Suo Zhang (Bulletin of Environmental Contamination and Toxicology, 2008)

Suppression of Sclerotinia sclerotiorum by antifungal substances produced by the mycoparasite Coniothyrium minitans - Rui Yang; Yong Chao Han; Guo Qing Li; Dao Hong Jiang; Hung Chang Huang (European Journal of Plant Pathology, 2007)

Genetic dissection of plant height by molecular markers using a population of recombinant inbred lines in maize - Tang Ji-hua; Teng Wen-tao; Yan Jian-bing; Ma Xi-qing; Meng Yi-jiang; Dai Jin-rui; Li Jian-Sheng (Euphytica, 2007)

Detection of known mutations in hypertrophic cardiomyopathy using oligonucleotide microarrays assisted by improved base stacking hybridization - Dong Wang; Yan Li; Rui Zhang; Di Jiang; Xuemei Ma; Yuxiang Zhou; Jing Cheng (Biotechnology Letters, 2003)

Crystal structure studies on rubrerythrin: enzymatic activity in relation to the zinc movement - Mei Li; Ming-yih Liu; Jean LeGall; Lu-lu Gui; Jun Liao; Tao Jiang; Ji-ping Zhang; Dong-cai Liang; Wen-rui Chang (JBIC Journal of Biological Inorganic Chemistry, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)